Lubricant composition and bearing

By using compounds containing specific aromatic ring structures and chain groups, the insufficient performance of existing lubricants in high temperature and high vacuum environments is solved, and efficient and durable lubricating effects and conductivity are achieved.

CN116396791BActive Publication Date: 2025-03-04NIPPON THOMPSON +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
CN202310269356.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2018-08-23
Filing Date
2019-07-16
Publication Date
2025-03-04
Estimated Expiration
2039-07-16

AI Technical Summary

Technical Problem

The existing lubricants are not ideal in terms of lubricity, heat resistance, low evaporation after long-term use, electrical conductivity and clean appearance, especially in high temperature and high vacuum environments.

Method used

A compound containing a specific aromatic ring structure and chain groups is used as a lubricant, which is in a smectic liquid crystal phase over a wide temperature range, has electrical conductivity, and reduces decomposition and evaporation through a properly designed chemical structure.

Benefits of technology

It has achieved low friction coefficient in a wide temperature range (-50℃~+300℃), excellent heat resistance, significant conductivity, less loss after long-term use, and has clean appearance and fluorescence characteristics, which are suitable for high temperature and high vacuum environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116396791B_ABST
    Figure CN116396791B_ABST
Patent Text Reader

Abstract

Provided are a lubricant composition suitable for use in a clean environment requiring low dust generation, in a high vacuum such as space, or at a high temperature, and a bearing enclosed with the lubricant composition. A lubricant composition comprising a 2-ring liquid crystal compound and a 3-ring liquid crystal compound, wherein the 2-ring liquid crystal compound substantially contains only at least one of the 2-ring liquid crystal compounds represented by the following formula (1), and the 3-ring liquid crystal compound substantially contains only at least one of the 3-ring liquid crystal compounds represented by the following formula (2), wherein the mixing ratio of the 2-ring liquid crystal compound to the 3-ring liquid crystal compound is 95:5 to 15:85 by mass ratio, wherein in formula (1), R 1 and R 2 are the same or different and are groups ‑OCH2CH2CH(R')CH2CH2OR, where R 11 and R 21 the same or different, is a group ‑OR, R 12 , R 13 , R 22 and R 23 The same or different, is hydrogen, or a group ‑OR. #imgabs0#
Need to check novelty before this filing date? Find Prior Art

Description

[0001] This application is a divisional application of a patent application with an application date of July 16, 2019, application number 201980047432.9, and invention name “Conductive Lubricant” (application number 202210387876.0, invention name “Conductive Lubricant”). Technical Field

[0002] The present invention relates to conductive lubricants. Background Art

[0003] Lubricants are substances that are usually applied to the moving parts of a machine to reduce friction between contacting parts, prevent the generation of frictional heat, and suppress the concentration of stress on the contact parts between parts. They also have the functions of sealing, rust prevention, and dust prevention. Lubricants include lubricating oils and greases, and lubricating oils are usually mixed oils such as petroleum purifications. Greases are substances that retain lubricating oils in a thickener and give thixotropy for the purpose of being applied to sliding surfaces that are difficult to maintain a lubricant film (such as sliding bearings and rolling bearings).

[0004] Such lubricants are required to have various properties, not only a low friction coefficient, but also a wide temperature range in which they can be used, and little loss due to evaporation or decomposition over a long period of time. In addition, it is advantageous for the lubricant to have conductivity that can release static electricity generated between parts due to rotational friction, so it would be very useful if a lubricant with conductivity could be obtained without mixing carbon, metal powder, etc.

[0005] Patent Documents 1 and 2 disclose a diester type lubricating oil compound having an ester structure at both ends of the molecule. In addition, Patent Documents 3 to 6 propose the use of a liquid crystal compound as a lubricant. Patent Document 7 describes a lubricant containing a liquid crystal compound having conductivity, but it cannot be said that it is a compound that exhibits liquid crystal properties at room temperature.

[0006] Prior art literature

[0007] Patent Literature

[0008] Patent Document 1: Japanese Patent Re-publication No. WO2011 / 125842

[0009] Patent Document 2: Japanese Patent Application Publication No. 2013-82900

[0010] Patent Document 3: Japanese Patent Application Laid-Open No. 6-128582

[0011] Patent Document 4: Japanese Patent Application Publication No. 2004-359848

[0012] Patent Document 5: Japanese Patent Application Publication No. 2005-139398

[0013] Patent Document 6: Japanese Patent Application Publication No. 2008-214603

[0014] Patent Document 7: Japanese Patent Application Publication No. 2017-105874 Summary of the invention

[0015] Problem that the invention aims to solve

[0016] However, as a lubricant to replace conventional grease, improvements in lubricity (low friction coefficient), heat resistance, durability with low evaporation over a long period of time, conductivity that can release static electricity generated between parts due to rotational friction, and a clean appearance due to the absence of carbon or metal powder are insufficient.

[0017] Therefore, an object of the present invention is to provide a lubricant which has conductivity even without compounding carbon, metal powder, or the like, is effective in a wide temperature range, and has little loss due to evaporation, decomposition, or the like over a long period of time.

[0018] Specifically, regarding heat resistance, it is expected to be stable at a temperature of 140°C or higher, preferably 200°C or higher, more preferably 230°C or higher, further preferably 250°C or higher, and most preferably 300°C or higher. On the other hand, as a low-temperature characteristic, it is expected to be usable down to 30°C or lower, preferably around -50°C. In addition, regarding electrical conductivity, it is required to be at least capable of discharging static electricity generated between components due to rotational friction. For example, it is expected to inject static electricity into an electrode area of ​​1 cm 2 When a voltage of 5 V is applied between the electrodes in a battery cell having an inter-electrode distance of 5 μm, the conductivity is 0.001 μA or more, more preferably 0.01 μA or more, and further preferably 0.07 μA or more in the range of 30° C. to 300° C.

[0019] Furthermore, it is not necessary to add carbon or metal to impart conductivity, thereby satisfying economic rationality, and it has a clean appearance at the beginning of use, so there is an advantage that oxidation degradation (yellowing) can be discovered early. Furthermore, the compound itself is a fluorescent substance, so there is also an advantage that, for example, bad conditions such as lubricant leakage can be immediately discovered by irradiating light from a black light lamp that emits long-wavelength ultraviolet rays. Of course, it is necessary to satisfy the original lubrication performance, and it is expected that the dynamic friction coefficient is 0.13 or less.

[0020] Furthermore, it is desirable to achieve the above-mentioned properties by mixing as few, preferably one or two, and most preferably one liquid crystal compound as possible rather than mixing a plurality of lubricating liquid crystal compounds. To this end, it is important to appropriately design the chemical structure of the compound that exhibits liquid crystal properties over a wide temperature range.

[0021] Furthermore, when used in an environment where replacement of the lubricant is extremely difficult, such as in wind power generation, polar regions, and space-related applications, a lubricant that has little loss due to evaporation, decomposition, etc. over a long period of time is very useful.

[0022] Solutions for solving problems

[0023] The present inventors have conducted intensive studies to solve the above problems and have found that a compound having a specific aromatic ring structure having conductivity and a specific chain group having lubricity linked to the ring structure appropriately arranged in one molecule can achieve the above object, thereby completing the present invention.

[0024] That is, the present invention includes the following.

[0025] [1] A conductive lubricant comprising at least one compound (1) represented by formula (1):

[0026]

[0027] [Wherein,

[0028] R 11 and R 21 are the same or different and are hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0029] R 12 , R 13 , R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)].

[0030] [2] The conductive lubricant according to [1], comprising a compound (1) represented by formula (1), wherein R 11 , R 12 , R 13 , R 21 , R 22 and R 23 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 4≤n≤12).

[0031] [3] The conductive lubricant according to [2], comprising a compound (1) represented by formula (1), wherein R 11 , R 12 and R 13 Relative to the -CH=CH- group, R 21 , R 22 and R 23 Substitution is carried out at the para position and two meta positions relative to the -CH=CH- group.

[0032] [4] The conductive lubricant according to [1], comprising two or more compounds (1) represented by formula (1), wherein R 11 and R 21 For hydrogen,

[0033] R 12 , R 13 , R 22 and R 23 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl).

[0034] [5] The conductive lubricant according to [4], comprising two or more compounds (1) represented by formula (1), wherein R 12 and R 13 Relative to the -CH=CH- group, R 22 and R 23 The substitution is carried out at the para position and 1 meta position relative to the -CH=CH- group.

[0035] [6] The conductive lubricant according to any one of [1] to [5], wherein the group bonded to -CH=CH- in formula (1) is in a trans positional relationship.

[0036] [7] The conductive lubricant according to [1], wherein the compound (1) represented by the formula (1) is in a smectic liquid crystal phase in the temperature range of -50°C to +300°C.

[0037] [8] The conductive lubricant according to any one of [1] to [7], wherein the conductive lubricant is injected into the electrode area of ​​1 cm 2 When a voltage of 5 V is applied between the electrodes in a battery cell having an inter-electrode distance of 5 μm, the conductivity is 0.07 μA or more in a temperature range of 30° C. to 300° C.

[0038] [9] The conductive lubricant according to [2] or [3], wherein the conductive lubricant is injected into the electrode area of ​​1 cm 2 When a voltage of 5 V is applied between the electrodes in a battery cell with an inter-electrode distance of 5 μm, the conductivity is 10,000 μA or more in a temperature range of 30° C. to 90° C.

[0039]

[10] The conductive lubricant according to any one of [1] to [9], which does not contain any of carbon and metal.

[0040]

[11] The conductive lubricant according to any one of [1] to

[10] , wherein the compound (1) represented by the formula (1) is a fluorescent substance.

[0041]

[12] The conductive lubricant according to any one of [1] to

[11] , wherein the compound (1) represented by formula (1) is a trans isomer represented by formula (1′):

[0042]

[0043] [Where R 11 , R 12 , R 13 , R 21 , R 22 and R 23 With R in formula (1) 11 , R 12 , R 13 , R 21 , R 22 and R 23 have the same meaning].

[0044]

[13] Use of the compound (1) represented by formula (1) in the manufacture of a conductive lubricant,

[0045]

[0046] [Wherein,

[0047] R 11 and R 21are the same or different and are hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0048] R 12 , R 13 , R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)].

[0049]

[14] A mechanical device comprising: a plurality of mechanical elements that contact each other and move relative to each other; and a conductive lubricant according to any one of [1] to

[12] disposed on at least a portion of a contact surface of the mechanical elements.

[0050] Effects of the Invention

[0051] According to the present invention, a new type of lubricant is provided, which has a low friction coefficient, excellent heat resistance, a lubricating effect in a wide temperature range (at least -50°C to +300°C), little loss over a long period of time, conductivity even without mixing with carbon powder, metal powder, etc., emits fluorescence through ultraviolet irradiation, and can replace commonly used grease without using a thickener. BRIEF DESCRIPTION OF THE DRAWINGS

[0052] Figure 1 The differential thermal analysis data of the compound for conductive lubricant of the present invention are shown.

[0053] Figure 2 This is a graph showing the conductivity of the compound for conductive lubricant of the present invention.

[0054] Figure 3 This is a diagram showing the fluorescence spectrum of the compound for conductive lubricant of the present invention.

[0055] Figure 4 A three-dimensional diagram of the bearing.

[0056] Figure 5 Schematic diagram of the apparatus used in the flowability test.

[0057] Figure 6 This is a graph showing the results of a saturated vapor pressure measurement test.

[0058] Figure 7 This is a diagram showing the results of a pressure measurement test at elevated temperature.

[0059] Figure 8 A three-dimensional diagram of a linear motion guide unit.

[0060] Fig. 9 It is a figure which shows the result of the dust generation test.

[0061] Fig.10 A three-dimensional diagram of the bearing.

[0062] Fig.11 Schematic diagram of the apparatus used in the flowability test.

[0063] Fig.12 This is a diagram showing the results of a pressure measurement test at elevated temperature.

[0064] Fig.13 A three-dimensional diagram of a linear motion guide unit.

[0065] Fig.14 It is a figure which shows the result of the dust generation test. DETAILED DESCRIPTION

[0066] According to the present invention, there is provided a conductive lubricant comprising at least one compound (1) represented by formula (1),

[0067]

[0068] [Wherein,

[0069] R 11 and R 21 are the same or different and are hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0070] R 12 , R 13 , R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H2n+1 , 4≤n≤12, R' is methyl or ethyl)].

[0071] The compound (1) represented by formula (1) is a compound in which a specific π-electron conjugated system core structure (1,4-bis[(phenyl)vinyl]benzene, hereinafter sometimes referred to as "three-ring skeleton structure") responsible for conductivity and a specific chain group responsible for lubricity connected to the core structure are appropriately arranged in one molecule.

[0072] In formula (1), the three-ring skeleton structure includes a conjugated system with 22 π electrons, and a rigid flat plate structure is formed by the expansion of the π electron conjugated system. Therefore, each molecule of compound (1) overlaps and gathers in a relatively thin manner in which the π electron conjugated system overlaps each other. As a result, compound (1) can form a liquid crystal phase (particularly a smectic liquid crystal phase) within a desired temperature range (specifically shown in the examples described later). In this way, the three-ring skeleton structure becomes a liquid crystal forming element (core structure) in compound (1), and compound (1) exerts conductivity by virtue of the overlapping π electron conjugated system.

[0073] [Chain group R 11 , R 12 , R 13 , R 21 , R 22 and R 23 ]

[0074] In formula (1), R 11 , R 12 , R 13 , R 21 , R 22 and R 23 It is a chain group connected to the core structure and responsible for the lubricity of the molecule.

[0075] R 11 and R 21 are the same or different and are hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, preferably 6≤n≤10, R' is methyl or ethyl, preferably methyl),

[0076] R 12 , R 13 , R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, preferably 6≤n≤10, R' is methyl or ethyl, preferably methyl).

[0077] Examples of R include n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl, 1-ethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl-n-butyl, 2,2-dimethyl-n-butyl 2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, n-heptyl, 1-methyl-n-hexyl, 2-methyl-n-hexyl, 3-methyl-n-hexyl, 1,1-dimethyl-n-pentyl, 1,2-dimethyl-n-pentyl, 1,3-dimethyl-n-pentyl, 2,2-dimethyl 1-ethyl-n-pentyl, 2-ethyl-n-pentyl, 3-ethyl-n-pentyl, 1-methyl-1-ethyl-n-butyl, 1-methyl-2-ethyl-n-butyl, 1-ethyl-2-methyl-n-butyl, 2-methyl-2-ethyl-n-butyl, 2-ethyl-3-methyl-n-butyl, n-octyl, 1-methyl-n-heptyl, 2-methyl-n-heptyl, 3-methyl-n-heptyl, 1,1-dimethyl-n-hexyl, 1,2-dimethyl-n-hexyl , 1,3-dimethyl-n-hexyl, 2,2-dimethyl-n-hexyl, 2,3-dimethyl-n-hexyl, 3,3-dimethyl-n-hexyl, 1-ethyl-n-hexyl, 2-ethyl-n-hexyl, 3-ethyl-n-hexyl, 1-methyl-1-ethyl-n-pentyl, 1-methyl-2-ethyl-n-pentyl, 1-methyl-3-ethyl-n-pentyl, 2-methyl-2-ethyl-n-pentyl, 2-methyl-3-ethyl-n-pentyl, 3-methyl-3-ethyl-n-pentyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.

[0078] R may be a branched chain, but is preferably bulky enough to prevent close assembly of the molecules of the compound (1) and not to impair the function of the above-mentioned three-ring skeleton structure, namely, the function of exerting conductivity by means of the overlapping π-electron conjugated system.

[0079] By appropriately selecting the chain group R 11 , R12 , R 13 , R 21 , R 22 and R 23 , thereby adjusting the size (long diameter) and polarity of the entire molecule. The following describes particularly preferred selections.

[0080] [R 11 and R 21 is hydrogen, R 12 , R 13 , R 22 and R 23 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 Compounds of OR]

[0081] R 11 and R 21 When it is hydrogen, the total number of substituents on the benzene rings at both ends of the tricyclic skeleton structure is 4. Hereinafter, such a compound may be referred to as a "quaternary substituted compound".

[0082] 4 substituents other than hydrogen (R 12 , R 13 , R 22 and R 23 ) can also be arranged asymmetrically in a manner such that three benzene rings are arranged at one end of the three-ring skeleton structure and one benzene ring is arranged at the other end. For the convenience of synthesis, it is convenient to arrange it symmetrically in a manner such that two benzene rings are arranged at one end of the three-ring skeleton structure and two benzene rings are arranged at the other end.

[0083] In this case, the substitution positions include 2,3-, 2,4-, 2,5-, 2,6-, 3,4-, and 3,5-, and the substitution at the 3,4 position is preferred, of each benzene ring.

[0084] The tetra-substituted compound having substituents at the 3- and 4-positions of each benzene ring has the following stereoisomers. In the present invention, one of these may be used or a mixture of both may be used.

[0085]

[0086] [R 11 , R 12 , R 13 , R 21 , R 22 and R 23 is a compound containing a group -OR]

[0087] R 11 , R12 , R 13 , R 21 , R 22 and R 23 In the case of the group -OR, the total number of substituents on the benzene rings at both ends of the tricyclic skeleton structure is 6. Hereinafter, such a compound may be referred to as a "6-substituted compound".

[0088] 6 substituents (R 11 , R 12 , R 13 , R 21 , R 22 and R 23 ) can also be arranged asymmetrically in a manner such that 4 benzene rings are arranged at one end of the 3-ring skeleton structure and 2 benzene rings are arranged at the other end, but for the convenience of synthesis, it is convenient to arrange it symmetrically in a manner such that 3 benzene rings are arranged at one end of the 3-ring skeleton structure and 3 benzene rings are arranged at the other end.

[0089] In this case, the substitution positions are 2,3,4-, 2,3,5-, 2,4,5-, 3,4,5-, 2,3,6-, and 2,4,6- of each benzene ring, but substitution at the 3,4,5 positions is preferred as follows.

[0090]

[0091] In the present invention, the compound (1) represented by formula (1) may be used alone or in combination of two or more thereof. Examples include: a method of mixing two or more tetra-substituted compounds, a method of mixing one or more tetra-substituted compounds with one or more hexa-substituted compounds, and a method of using a tetra-substituted compound or a hexa-substituted compound alone.

[0092] [Synthesis of Compounds]

[0093] The method for producing the compound (1) represented by the formula (1) of the present invention is not particularly limited, and the compound (1) can be synthesized by combining known reactions.

[0094] The following method can be used: using an alcohol compound (such as R 12 -OH), phenolic compounds (such as HO-[3-ring skeleton structure]-OH) and alkali metals, alkali metal alkoxides, and halogen compounds (such as R 12 -X, X-[3-ring skeleton structure]-X (X is a halogen atom such as a chlorine atom, a bromine atom or an iodine atom)). For example, it can be prepared according to the method described in Japanese Patent No. 5916916.

[0095] In particular, the compound (1) represented by the formula (1) of the present invention can be produced as follows.

[0096] At least one compound represented by the following formula

[0097]

[0098] [Wherein,

[0099] R 11 is hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0100] R 12 and R 13 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)],

[0101] At least one compound represented by the formula

[0102]

[0103] [Wherein,

[0104] R 21 is hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl,

[0105] R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)],

[0106] And the compound represented by the following formula

[0107]

[0108] Under appropriate reaction conditions, a mixture of the following compounds in a molar ratio of 1:2:1 is obtained.

[0109] [Where R 11 , R 12 , R 13 , R 21 , R 22 and R 23 as defined above].

[0110] Examples of the alkali metal include potassium carbonate, potassium hydroxide, sodium hydroxide, and the like. Examples of the alkali metal alkoxide include sodium ethoxide, sodium methoxide, sodium tert-butoxide, potassium tert-butoxide, and the like.

[0111] In addition, various conventionally known organic solvents can be used in the above reaction, for example, diethyl ether, tetrahydrofuran (THF), acetone, and toluene can be used.

[0112] As another method, it can also be prepared as follows.

[0113] At least one compound represented by the following formula

[0114]

[0115] [Wherein,

[0116] R 11 is hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0117] R 12 and R 13 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)],

[0118] At least one compound represented by the formula

[0119]

[0120] [Wherein,

[0121] R 21 is hydrogen, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl),

[0122] R 22 and R 23 The same or different, a group -OR or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 4≤n≤12, R' is methyl or ethyl)],

[0123] And terephthalaldehyde shown in the following formula

[0124]

[0125] Under appropriate reaction conditions, a mixture of the following compounds in a molar ratio of 1:2:1 is obtained.

[0126] [Where R 11 , R 12 , R 13 , R 21 , R 22 and R 23 as defined above].

[0127] [Characteristics of conductive lubricants]

[0128] The conductive lubricant of the present invention preferably has an average dynamic friction coefficient of 0.13 or less when measured at 100°C.

[0129] The conductive lubricant of the present invention is injected into the electrode area of ​​1cm 2, when a voltage of 5V is applied between the electrodes in a battery cell with an inter-electrode distance of 5μm, the conductivity is preferably 0.001μA or more, more preferably 0.01μA or more, and further preferably 0.07μA or more in the range of 30°C to 300°C. There is no need to deliberately mix carbon, metal powder, etc. to exert such conductivity. Therefore, the appearance of the conductive lubricant of the present invention is extremely clean, and oxidation degradation (yellowing) due to long-term continuous use can be detected at an early stage. Furthermore, the compound itself is a fluorescent substance, so that it is also possible to immediately detect adverse conditions such as lubricant leakage by, for example, irradiating light from an electric lamp that emits long-wavelength ultraviolet rays, i.e., a black light lamp.

[0130] In addition, the conductive lubricant of the present invention has very low volatility (for example, the weight loss after heating at 100°C for one month is less than 1%), and has the advantage of being able to be used continuously for a long time without having to be replenished, compared to conventional greases.

[0131] When the conductive lubricant of the present invention is used for the purpose of applying a common grease, the conductive lubricant of the present invention does not need to use a thickener. This can not only shorten the production process, but also avoid the problem of reduced water resistance and shear stability that is easily caused by inappropriate selection of a thickener.

[0132] [Preparation of conductive lubricant]

[0133] The other components that can be included in the conductive lubricant of the present invention within the scope that does not impair the effect of the present invention are described in sequence. They are basically substances that are previously known as components contained in lubricants, and unless otherwise specified, the content thereof can be appropriately selected by those skilled in the art within the previously known range. In addition, any component can be used alone or in combination of two or more.

[0134] (Liquid Crystalline Compounds)

[0135] The compound (1) of the present invention is a liquid crystal compound, but the conductive lubricant of the present invention may contain other liquid crystal compounds.

[0136] Examples of such liquid crystal compounds include liquid crystal compounds that exhibit a smectic phase or a nematic phase, compounds having a structure of an alkylsulfonic acid or perfluorosulfonic acid film system, alkylcarboxylic acids, alkylsulfonic acids, etc. In addition, liquid crystal compounds described in Japanese Patent No. 5916916 and Japanese Unexamined Patent Application No. 2017-105874 may be appropriately blended.

[0137] The combined use of these components can further expand the temperature range in which the liquid crystal compound contained in the conductive lubricant of the present invention forms a liquid crystal phase, and there is a possibility that the advantages based on the formation of the liquid crystal phase can be enjoyed in a wide temperature range.

[0138] (Base oil)

[0139] When the compound (1) of the present invention is contained in a conductive lubricant as an additive, various conventionally known lubricant base oils can be used as the base oil.

[0140] The base oil is not particularly limited, and examples thereof include mineral oil, highly purified mineral oil, synthetic hydrocarbon oil, paraffinic mineral oil, alkyl diphenyl ether oil, ester oil, silicone oil, naphthenic mineral oil, and fluorinated oil. The content of such base oil in the conductive lubricant of the present invention is usually 80 to 99% by weight.

[0141] (Other additives)

[0142] When the compound of the present invention is contained in a lubricant as a base oil, various conventionally known additives may be added.

[0143] In addition, examples of additives that can be added to the conductive lubricant of the present invention include various additives used in lubricants such as bearing oil, gear oil and working oil, namely, extreme pressure agents, oriented adsorbents, antiwear agents, wear regulators, oiliness agents, antioxidants, viscosity index improvers, pour point depressants, detergent dispersants, metal deactivators, corrosion inhibitors, rust inhibitors, defoaming agents, solid lubricants, etc.

[0144] Examples of the extreme pressure agent include chlorine compounds, sulfur compounds, phosphoric acid compounds, hydroxycarboxylic acid derivatives, and organic metal extreme pressure agents. The addition of the extreme pressure agent improves the wear resistance of the conductive lubricant of the present invention.

[0145] Examples of the above-mentioned alignment adsorbent include silane coupling agents, titanium coupling agents, aluminum coupling agents, and various coupling agents represented by organic silane, organic titanium, organic aluminum, etc. By adding the alignment adsorbent, the liquid crystal alignment of the liquid crystal compound contained in the conductive lubricant of the present invention is enhanced, and the thickness and strength of the film formed by the conductive lubricant of the present invention can be enhanced.

[0146] The conductive lubricant of the present invention can be prepared by mixing the compound of the present invention described above and other components by a conventionally known method. An example of a method for preparing the conductive lubricant of the present invention is as follows.

[0147] The components of the conductive lubricant are mixed by a conventional method, and then subjected to a roll mill, degassing treatment, filter treatment, etc. as needed to obtain the conductive lubricant of the present invention. Alternatively, the conductive lubricant may be prepared by first mixing the oil component of the conductive lubricant, then adding other components such as additives and mixing, and then subjecting the above-mentioned degassing treatment, etc. as needed.

[0148] [Application of conductive lubricant]

[0149] As described above, the conductive lubricant of the present invention exhibits a good low viscosity in a wide temperature range and has a small dynamic friction coefficient. Therefore, it can be used as a lubricant in various mechanical devices that have conventionally used grease.

[0150] Mechanical devices usually have multiple mechanical elements that contact each other and move relative to each other, but by configuring the conductive lubricant of the present invention on at least a portion of the contact surface of the mechanical element, the friction generated by the contact of the aforementioned multiple mechanical elements is reduced, thereby making the relative movement smooth.

[0151] In the present invention, the aforementioned contact refers not only to the case where multiple objects are in direct contact, but also includes the case where they are in indirect contact by being sandwiched by any substance such as a coating formed by the conductive lubricant of the present invention. That is, when the conductive lubricant of the present invention is arranged on the contact surface of multiple mechanical elements, the coating formed by the composition is formed between the multiple mechanical elements, and the direct contact of the mechanical elements disappears. Thus, it is suitable to prevent wear and adhesion caused by friction between mechanical elements.

[0152] The method of disposing the conductive lubricant of the present invention on the contact surfaces of the aforementioned multiple mechanical elements is well known to those skilled in the art. Examples of such methods include: coating the aforementioned contact surfaces with the composition, and filling a certain area including the contact surfaces of the aforementioned mechanical elements and to which the mechanical elements are close with the aforementioned composition.

[0153] In addition, the aforementioned mechanical elements refer to elements (components, etc.) that constitute various mechanical devices, including: mechanical elements that have been lubricated with lubricants in the past, especially mechanical elements that have used grease, and mechanical elements that may be lubricated with lubricants, especially grease, in the future.

[0154] The contact surfaces of the aforementioned multiple mechanical elements, or more generally, the contact parts of the mechanical elements, may be flat or curved, and at least a portion of such surfaces may be concave and convex, or may have holes. Moreover, various surface treatments such as modifications may be applied to the parts of the mechanical elements constituting the contact parts of the mechanical elements. The material of the mechanical elements is not particularly limited, and may be composed of any material such as metal materials or organic / inorganic materials. In addition, the types of constituent materials may be different in one and the other of the mechanical elements.

[0155] Examples of mechanical devices having such various mechanical elements include transportation machines, processing machines, computer-related equipment, office-related equipment such as copying machines, and household products. The conductive lubricant of the present invention can be suitably used for lubricating bearings of these various mechanical devices.

[0156] Specific examples of the aforementioned bearings include: bearings used in automotive electrical components such as electric fan motors and wiper motors; rolling bearings used in drive systems such as automobile engine auxiliaries such as water pumps and electromagnetic clutch devices; rolling bearings used in rotating devices such as small or large general-purpose motors for industrial machinery; high-speed and high-precision rotating bearings such as spindle bearings for working machinery, and rolling bearings used in motors and rotating devices for household electrical products such as air-conditioning fan motors and washing machines; rolling bearings used in rotating parts of computer-related equipment such as HDD devices and DVD devices; rolling bearings used in rotating parts of office equipment such as copiers and automatic ticket checking devices; and axle bearings for trams and trucks.

[0157] The conductive lubricant of the present invention can also be used for resin-free lubrication used in automotive CVJ devices, power steering devices for electronic and electrical control, and lubrication of mechanical parts of various rolling devices such as linear guides and ball screws.

[0158] The conductive lubricant of the present invention can also be used, for example, in engine oils, gear oils, automotive oils, lubricating oils for ships and aircraft, engine oils, turbine oils, hydraulic oils, spindle oils, compressor and vacuum pump oils, refrigerator oils, and lubricating oils for metalworking, as well as hinge oils, sewing oils, and sliding surface oils, and further, lubricants for disks of HDD devices (including lubricants used in perpendicular magnetic recording methods that utilize horizontal magnetic recording methods and thermally assisted recording technologies), lubricants for magnetic recording media, lubricants for micromachines, and lubricants for artificial bones. In addition, when used in an environment where it is extremely difficult to replace the lubricant, such as in wind power generation, polar regions, and space-related applications, the lubricant of the present invention is particularly useful because it has little loss due to evaporation, decomposition, etc. over a long period of time.

[0159] Example

[0160] Hereinafter, the present invention will be described in further detail based on examples, but the present invention is not limited to these examples at all.

[0161] [Measurement of various physical properties]

[0162] Various physical properties of the test products were measured according to the following methods.

[0163] (Structure confirmation of compound)

[0164] 1H-NMR was used.

[0165] (Dynamic friction coefficient of the compound)

[0166] The dynamic friction coefficient of the compound can be measured using a commercially available dynamic friction coefficient measuring device, but in this specification, the dynamic friction coefficient is measured using a surface property measuring machine "TYPE: 14FW" manufactured by Shinto Scientific Co., Ltd.

[0167] The dynamic friction coefficient of the compound of the present invention is affected by temperature, and therefore the dynamic friction coefficient is measured at a predetermined measurement temperature (100° C.).

[0168] Specifically, a stainless steel plate is fixed on the moving stage of the surface property measuring machine and a sample is suspended. Under the following conditions, a fixed ball is used to apply point pressure, and wear based on reciprocating motion is repeated. The dynamic friction coefficient of each 100 reciprocating times is measured to 1800 times, and their average value (average dynamic friction coefficient) is calculated. This average value is used as the average dynamic friction coefficient of the compound of the present invention.

[0169] The measurement conditions are as follows.

[0170] Vertical load: 100g

[0171] Friction speed: 600 mm / min

[0172] Reciprocating times: 1800

[0173] Reciprocating stroke: 5mm

[0174] Load converter capacity: 19.61N

[0175] Friction material: SUS304 stainless steel ball diameter 10mm

[0176] Sample volume: 0.2 mL

[0177] (Liquid Crystallinity of Compounds)

[0178] By observing with a polarizing microscope, the glass state, liquid crystal state (smectic phase), etc. can be determined.

[0179] (Conductivity of Compounds)

[0180] The sample was injected into an area of ​​1 cm with a set distance between electrodes of 5 μm. 2 Advantest ADCMT 6241A was used as a voltage application current measuring device and METTLER FP900 Thermo System was used as a temperature controller to measure the current value at an applied voltage of 5 V and a temperature range of 30° C. to 300° C. The measurement was performed twice each to confirm the fixation of the liquid crystal.

[0181] (Fluorescence spectrum of the compound)

[0182] The measurement was performed using a F-7000 spectrofluorophotometer (manufactured by Hitachi High-Tech Science Corporation) under the following conditions.

[0183] Excitation wavelength: 371.0nm

[0184] Fluorescence start wavelength: 200.0nm

[0185] Fluorescence end wavelength: 700.0nm

[0186] Scanning speed: 240nm / min

[0187] Excitation side slit: 5.0nm

[0188] Fluorescence side slit: 5.0nm

[0189] Photomultiplier tube voltage: 400V

[0190] [Synthesis of Compounds]

[0191] Synthesis examples of the compounds of the present invention are shown below.

[0192] [Synthesis Example 1 Synthesis of Liquid Crystal Compound (9-1)]

[0193] First, an aldehyde raw material is prepared.

[0194]

[0195] In a 500 mL Erlenmeyer flask, 5.5 g (0.040 mol) of 3,4-dihydroxybenzaldehyde (5) and 16.6 g (0.12 mol) of potassium carbonate were dissolved in 150 mL of DMF, and stirred at 50° C. for 1 hour in a silicon bath under a nitrogen atmosphere. Then, 27.0 g (0.10 mol) of the bromine compound (4-1) was added, and the mixture was stirred at 80° C. for 48 hours in a silicon bath.

[0196] The reaction solution was poured into 300 mL of 10% cold dilute hydrochloric acid and extracted with 300 mL of ether using a 1 L separatory funnel. The obtained ether layer was washed with 300 mL of distilled water. The water layer was extracted again with 100 mL of ether. The obtained ether layers were combined, anhydrous sodium sulfate was added, and dehydrated overnight.

[0197] Anhydrous sodium sulfate was removed by suction filtration, and the solvent was removed under reduced pressure in an evaporator. Unreacted bromine compound (4-1) was removed under reduced pressure in an evaporator (200°C oil bath). The residue was washed with methanol, and the target compound (6-1) was obtained from the soluble portion.

[0198] The results are described below.

[0199] Theoretical yield: 20.3g

[0200] Yield: 19.8g

[0201] Yield: 98%

[0202] Appearance: Brown solid

[0203] Next, a liquid crystal compound is obtained from the above-mentioned aldehyde raw material.

[0204]

[0205] In a 300 mL Erlenmeyer flask, 4.1 g (0.0080 mol) of the aldehyde compound (6-1), 1.5 g (0.0040 mol) of the compound (8), and 50 mL of THF as a solvent were added, and 1.4 g (0.012 mol) of potassium tert-butoxide dissolved in 50 mL of THF was added dropwise thereto, and the mixture was stirred at 30° C. for 24 hours under a nitrogen atmosphere.

[0206] After adding 5 mL of hydrochloric acid, THF was removed by evaporation under reduced pressure, and the obtained solid was then washed with methanol and hexane.

[0207] After that, the residue was dissolved in THF 10-20 mL, and 200 mL of distilled water was added for ultrasonic cleaning, and the mixture was placed in a refrigerator overnight. The target product precipitated on the wall of the container was obtained by decantation. It should be noted that if the amount of the target product is insufficient, the target product can also be obtained by concentrating the distilled water with an evaporator and then placing it in a refrigerator overnight. Column chromatography was performed as needed to obtain the target product (9-1).

[0208] The results are described below.

[0209] Theoretical yield: 4.3g

[0210] Yield: 1.7g

[0211] Yield: 40%

[0212] Appearance: Yellow, sticky solid

[0213] The structure of the compound of formula (9-1) synthesized according to the above method is shown below.

[0214] [Table 1]

[0215] Table 1

[0216]

[0217] [Synthesis Example 2 Synthesis of Liquid Crystal Compounds]

[0218] A halide raw material is prepared and coupled with terephthalaldehyde to obtain a liquid crystal compound.

[0219]

[0220] In a 300 mL conical flask, 1.94 g (0.015 mol) of terephthalaldehyde (1-8) and 19.93 g (0.03 mol) of compound (3-6) were dissolved in THF. 6.8 g (0.06 mol) of potassium tert-butoxide as a base was dissolved in 50 mL of THF and added dropwise at room temperature over 40 minutes. The mixture was then stirred overnight under a nitrogen atmosphere.

[0221] After the reaction, THF was removed under reduced pressure using an evaporator, 150 mL of methanol was added to the residue, and the methanol-insoluble portion was filtered out, and then ultrasonically cleaned with 100 mL of methanol several times to obtain the target product (3-7), which was then dried in vacuum overnight.

[0222] The results are described below.

[0223] Yield: 18.2g

[0224] Yield: 99.4%

[0225] Appearance: light yellow solid

[0226] The compound was purified by acetone to obtain a light yellow powder solid in which the two -CH=CH-bonded groups were both in a trans positional relationship (confirmed by 1H-NMR). It should be noted that by only being composed of trans isomers, it is easy to form aggregates, which are not easy to evaporate and can also improve conductivity. On the other hand, if cis isomers are included, there is a concern that this effect will be hindered.

[0227] [Liquid Crystalline Properties of Compounds]

[0228] The results of observing liquid crystallinity using a polarizing microscope are shown in the following table.

[0229] [Table 2]

[0230] Table 2

[0231]

[0232] G: Glass Sm: Smectic phase dec.: Decomposition

[0233] (The smectic phase on the low temperature side is referred to as Sm1, and the smectic phase on the high temperature side is referred to as Sm2)

[0234] It is found that the compound exhibits a smectic liquid crystal phase in a wide range of -50°C to +300°C or higher. The fact that the compound exhibits a liquid crystal phase at room temperature is one of the remarkable characteristics of the compound of the present invention.

[0235] The results of differential thermal analysis of compound No. [9-1-1] are shown in Figure 1The curve with an inflection point at 59.59°C is the DTA curve, and the curve that starts to drop from around 400°C is the TG curve. It shows that the structure changes around 60°C and around 420°C, but is stable between them. It is also one of the remarkable characteristics of the compound of the present invention that it does not cause evaporation or decomposition in the temperature range of 30°C to 300°C.

[0236] [Conductivity of Compounds]

[0237] The changes in conductivity of compound numbers [9-1-1], [9-1-2], [9-1-3], [9-1-4], and [9-1-5] due to temperature are shown in Tables 3 to 7 below.

[0238] [Table 3]

[0239] Table 3: Conductivity of compound number [9-1-1]

[0240] Temperature(℃) Voltage (V) Current value (μA) Temperature(℃) Voltage (V) Current value (μA) 30 5 6.0026 170 5 4.8944 40 5 0.0159 180 5 6.1288 50 5 0.058B 190 5 8.0835 60 5 2.1968 200 5 11.5971 70 5 0.1094 210 5 16.5058 80 5 0.1375 220 5 19.1733 90 5 17.8538 230 5 14.7291 100 5 1.5771 240 5 9.665 110 5 4.207 250 5 8.101 120 5 1.882 260 5 13.52 130 5 1.7654 270 5 8.6681 140 5 2.4169 280 5 5.8342 150 5 3.2754 290 5 4.7632 160 5 4.1522 300 5 4.7254

[0241] [Table 4]

[0242] Table 4: Conductivity of compound number [9-1-2]

[0243] Temperature(℃) Voltage (V) Current value (μA) Temperature(℃) Voltage (V) Current value (μA) 30 5 1.271 170 5 1.4788 40 5 0.3639 180 5 1.4877 50 5 0.134 190 5 1.7764 60 5 0.252 200 5 1.1221 70 5 0.315 210 5 1.6562 80 5 0.3018 220 5 2.896 90 5 4.4199 230 5 1.5948 100 5 2.6547 240 5 1.6807 110 5 3.1428 250 5 1.6522 120 5 0.9698 260 5 2.6974 130 5 2.5159 270 5 2.5657 140 5 1.8648 280 5 3.5319 150 5 1.1846 290 5 4.2076 160 5 1.193 300 5 4.474

[0244] [Table 5]

[0245] Table 5: Conductivity of compound number [9-1-3]

[0246] Temperature(℃) Voltage (V) Current value (μA) Temperature(℃) Voltage (V) Current value (μA) 30 5 0.4974 170 5 0.2891 40 5 0.2104 180 5 0.3344 50 5 0.073 190 5 0.3864 60 5 0.1714 200 5 0.4311 70 5 0.2571 210 5 0.4567 80 5 0.1514 220 5 0.4779 90 5 0.1697 230 5 0.5196 100 5 0.1407 240 5 0.4994 110 5 0.249 250 5 0.4883 120 5 0.353 260 5 0.4551 130 5 0.3509 270 5 0.4683 140 5 0.5664 280 5 0.4899 150 5 0.2277 290 5 0.5577 160 5 0.2179 300 5 0.6964

[0247] [Table 6]

[0248] Table 6: Conductivity of compound number [9-1-4]

[0249] Temperature(℃) Voltage (V) Current value (μA) Temperature(℃) Voltage (V) Current value (μA) 30 5 5.6613 170 5 0.5847 40 5 2.4862 180 5 0.6529 50 5 4.3051 190 5 0.7263 60 5 2.2892 200 5 0.8055 70 5 4.1668 210 5 0.8873 80 5 2.4289 220 5 1.0147 90 5 7.3336 230 5 1.0852 100 5 3.208 240 5 1.1924 110 5 2.9132 250 5 1.3158 120 5 0.4281 260 5 1.5462 130 5 0.9032 270 5 1.7639 140 5 4.1524 280 5 2.1459 150 5 3.2689 290 5 2.5774 160 5 0.5141 300 5 3.1378

[0250] [Table 7]

[0251] Table 7: Conductivity of compound number [9-1-5]

[0252] Temperature(℃) Voltage (V) Current value (μA) Temperature(℃) Voltage (V) Current value (μA) 30 5 12.7121 170 5 11.415 40 5 10.265 180 5 3.2614 50 5 7.0502 190 5 2.594 60 5 5.6576 200 5 2.7403 70 5 3.6713 210 5 3.1234 80 5 3.8685 220 5 3.5099 90 5 6.141 230 5 4.039 100 5 9.5427 240 5 4.6312 110 5 10.4277 250 5 5.2222 120 5 8.4399 260 5 7.9326 130 5 12.2677 270 5 8.3911 140 5 16.9047 280 5 8.8213 150 5 21.2201 290 5 7.8095 160 5 18.2195 300 5 8.0776

[0253] Thus, one of the remarkable characteristics of the compound of the present invention is that it exhibits electrical conductivity in a wide temperature range of 30°C to 300°C. The change in electrical conductivity of compound No. [3-7] due to temperature is shown in Figure 2The compound having three substituents on each of the benzene rings at both ends has a remarkable feature in that it exhibits high conductivity of 10000 μA or more in the range of 30°C to 90°C and 7500 μA or more in the range of 30°C to 100°C.

[0254] [Dynamic friction coefficient of compound]

[0255] The dynamic friction coefficient of compound No. [9-1-6] and DOS (the following structural formula: dioctyl sebacate) which has been widely used as a lubricating oil were measured. The results are shown in Table 8 below.

[0256]

[0257] [Table 8]

[0258] Table 8

[0259] Test product Average dynamic friction coefficient Compound [9-1-6] 0.120856 DOS 0.237602

[0260] [Fluorescence spectra of compounds]

[0261] The measurement results of the fluorescence spectra of compound numbers [9-1-3] and [9-1-4] are shown in Figure 3 (A) and (B). Peaks were observed at 420.8 nm and 443.6 nm, indicating that blue fluorescence was emitted. Compound Nos. [9-1-3] and [9-1-4] were irradiated with light from a black light lamp that emits long-wavelength ultraviolet light, and the presence or absence of the light emission was confirmed, so that adverse conditions such as lubricant leakage could be immediately detected, which is one of the remarkable characteristics of the compounds of the present invention.

[0262] Industrial Applicability

[0263] The liquid crystal compound of the present invention exhibits liquid crystal properties in a wide temperature range, maintains a low dynamic friction coefficient, has conductivity, has basically no loss caused by evaporation, decomposition, etc., has a clean appearance and emits fluorescence, and therefore has the characteristics of being able to immediately detect deterioration and leakage, and is therefore extremely useful as a conductive lubricant raw material.

[0264] Lubricants are substances that are usually applied to the moving parts of a machine to reduce friction between contacting parts, prevent the generation of frictional heat, and suppress the concentration of stress on the contact parts between parts. In addition, lubricants are substances that also perform the functions of sealing, rust prevention, and dust prevention. Lubricants include lubricating oils and greases. Lubricating oils are usually mixed oils such as petroleum purifications. On the other hand, greases are substances that keep lubricating oils in a thickener and give thixotropy for the purpose of being applied to sliding surfaces (such as sliding bearings and rolling bearings) that are difficult to keep in a state where a lubricant film is attached.

[0265] Such lubricants are required to have various properties, including a low friction coefficient and a wide temperature range in which they can be used and little loss due to evaporation or decomposition over a long period of time.

[0266] Patent document 1 describes a bearing lubricant that is a mixture of a liquid crystal compound and a grease. Patent documents 2 to 5 describe the following: By using a specific liquid crystal compound, a lubricant that is effective in a wide temperature range and evaporates less over a long period of time can be manufactured. Patent document 5 describes a heat-resistant conductive lubricant that is a liquid crystal mixture containing a mixture of a 2-ring liquid crystal compound and a 3-ring liquid crystal compound. According to the same document, the following is described: By mixing a 2-ring liquid crystal compound and a 3-ring liquid crystal compound in a ratio of 1:1, a lubricant that is liquid crystal in the range of -50°C to +220°C can be manufactured.

[0267] Prior art literature

[0268] Patent Literature

[0269] Patent Document 1: Japanese Patent Application Publication No. 2004-359848

[0270] Patent Document 2: Japanese Patent Application Publication No. 2015-199934

[0271] Patent Document 3: Japanese Patent Application Publication No. 2016-130316

[0272] Patent Document 4: Japanese Patent Application Publication No. 2016-150954

[0273] Patent Document 5: Japanese Patent Application Publication No. 2017-105874 [Summary of the invention]

[0275] [Problems to be solved by the invention]

[0276] An object of the present invention is to provide a lubricant composition suitable for use in a clean environment requiring low dust generation, in a high vacuum such as space, or at a high temperature, and a bearing enclosing the lubricant composition.

[0277] [Solutions to solve the problem]

[0278] The present inventors have found that a liquid crystal mixture having excellent performance as a lubricant can be obtained by mixing a two-ring liquid crystal compound and a three-ring liquid crystal compound having a certain specific structure in a specific ratio, and have completed the present invention. That is, the present invention includes the following. [1]

[0280] A lubricant composition comprising: at least one of the two-ring liquid crystal compounds represented by the following formula (1) and at least one of the three-ring liquid crystal compounds represented by the following formula (2), wherein the mixing ratio of the two-ring liquid crystal compound to the three-ring liquid crystal compound is 95:5 to 15:85 in terms of mass ratio.

[0281] Formula (1):

[0282]

[0283] [Wherein,

[0284] R 1 and R 2 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)]

[0285] Formula (2):

[0286]

[0287] [Wherein,

[0288] R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20),

[0289] R 12 , R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20)] [2]

[0291] The lubricant composition according to [1], wherein in the formula (1), 1≤n≤15, and R' is a methyl group. [3]

[0293] The lubricant composition according to [1] or [2], wherein the tricyclic liquid crystal compound is at least one of the compounds represented by the following formulae (3) to (5).

[0294] [4]

[0296] The lubricant composition according to any one of [1] to [3], comprising a larger amount of the bicyclic liquid crystal compound than the tricyclic liquid crystal compound. [5]

[0298] The lubricant composition according to any one of [1] to [4], wherein the residual rate after 600 hours in an atmosphere at a temperature of 100° C. is 95% or more. [6]

[0300] The lubricant composition according to any one of [1] to [5], which is -5 The remaining rate after 1000 hours in the atmosphere of Pa was 95% or more. [7]

[0302] A bearing enclosed with the lubricant composition described in any one of [1] to [6].

[0303] [Effects of the Invention]

[0304] According to the present invention, there can be provided a lubricant composition suitable for use in a clean environment, under a high vacuum, or under a high temperature, and a bearing enclosing the lubricant composition.

[0305] According to the present invention, there is provided a lubricant composition comprising: at least one of the two-ring liquid crystal compounds represented by the following formula (1) and at least one of the three-ring liquid crystal compounds represented by the following formula (2), wherein the mixing ratio of the two-ring liquid crystal compound to the three-ring liquid crystal compound is 95:5 to 15:85 in terms of mass ratio.

[0306] Formula (1):

[0307]

[0308] [Wherein,

[0309] R 1 and R 2 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)]

[0310] Formula (2):

[0311]

[0312] [Wherein,

[0313] R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20),

[0314] R 12 , R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20)]

[0315] In formulas (1) and (2), R 1 , R 2 , R 11 , R 12 , R 13 , R 21 , R 22 and R 23 Connected to the core structure, it is a chain group that takes on the lubricity of the molecule. 1 , R 2 , R 11 , R 12 , R 13 , R 21 , R 22 and R 23 , thereby adjusting the overall size (long diameter) and polarity of the molecule.

[0316] Examples of R in formulas (1) and (2) include n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl 1-ethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, n-heptyl, 1-methyl-n-hexyl, 2-methyl-n-hexyl, 3-methyl-n-hexyl, 1,1-dimethyl-n-pentyl, 1,2-dimethyl-n-pentyl, 1,3-dimethyl-n-pentyl, 2 ,2-dimethyl-n-pentyl, 2,3-dimethyl-n-pentyl, 3,3-dimethyl-n-pentyl, 1-ethyl-n-pentyl, 2-ethyl-n-pentyl, 3-ethyl-n-pentyl, 1-methyl-1-ethyl-n-butyl, 1-methyl-2-ethyl-n-butyl, 1-ethyl-2-methyl-n-butyl, 2-methyl-2-ethyl-n-butyl, 2-ethyl-3-methyl-n-butyl, n-octyl, 1-methyl-n-heptyl, 2-methyl-n-heptyl, 3-methyl-n-heptyl, 1,1-dimethyl-n-hexyl, 1,2-dimethyl- n-Hexyl, 1,3-dimethyl-n-hexyl, 2,2-dimethyl-n-hexyl, 2,3-dimethyl-n-hexyl, 3,3-dimethyl-n-hexyl, 1-ethyl-n-hexyl, 2-ethyl-n-hexyl, 3-ethyl-n-hexyl, 1-methyl-1-ethyl-n-pentyl, 1-methyl-2-ethyl-n-pentyl, 1-methyl-3-ethyl-n-pentyl, 2-methyl-2-ethyl-n-pentyl, 2-methyl-3-ethyl-n-pentyl, 3-methyl-3-ethyl-n-pentyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.

[0317] In formula (1), R 1 and R 2 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, preferably 1≤n≤15, more preferably 4≤n≤12, particularly preferably 8≤n≤10, R' is methyl or ethyl).

[0318] In formula (1), preferably, 1≤n≤15, and R' is a methyl group.

[0319] In formula (2), R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 8≤n≤12).

[0320] In formula (2), R 12 , R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 8≤n≤12).

[0321] The three-ring liquid crystal compound represented by formula (2) is preferably at least one of the compounds represented by the following formulae (3) to (5).

[0322]

[0323] The bicyclic liquid crystal compound represented by formula (1) is preferably at least one of the compounds represented by the following formulae (6) to (8).

[0324]

[0325] In the present invention, the three-ring liquid crystal compound represented by formula (2) can be used alone or as a mixture of two or more thereof. For example, any of the compounds represented by formulas (3) to (5) can be used alone or as a mixture of two or more thereof. In addition, all of the compounds represented by formulas (3) to (5) can be mixed and used.

[0326] In the present invention, the two-ring liquid crystal compound represented by formula (1) can be used alone or as a mixture of two or more thereof. For example, any of the compounds represented by formulas (6) to (8) can be used alone or as a mixture of two or more thereof. In addition, all of the compounds represented by formulas (6) to (8) can be mixed and used.

[0327] The method for producing the 2-ring liquid crystal compound represented by formula (1) and the 3-ring liquid crystal compound represented by formula (2) is not particularly limited, and they can also be produced by combining known reactions. For example, they can be produced according to the method described in Japanese Patent Application Publication No. 2017-105874.

[0328] The lubricant composition of the present invention is very unlikely to evaporate (for example, the residual rate after 600 hours in an atmosphere at a temperature of 100° C. is 95% or more), and therefore has the advantage of being able to be used continuously for a long time without replenishment, compared to general-purpose greases.

[0329] The lubricant composition of the present invention is very difficult to evaporate under high vacuum (for example, at a temperature of 25°C and a pressure of 10 -5 Pa atmosphere after 1000 hours, the residual rate is 95% or more), so it can be suitably used in high vacuum conditions such as outer space.

[0330] The lubricant composition of the present invention has extremely low dust generation and can therefore be suitably used in, for example, a semiconductor manufacturing apparatus installed in a clean room requiring a high degree of cleanliness.

[0331] The lubricant composition of the present invention is not easy to evaporate and has low dust generation. In addition, the lubricant composition of the present invention can stably exert its performance under high vacuum and high temperature. Therefore, the lubricant composition of the present invention can exert excellent performance as a lubricant for bearings.

[0332] The bearings enclosed with the lubricant composition of the present invention can be suitably used in semiconductor manufacturing equipment installed in a clean room, for example. In addition, the bearings enclosed with the lubricant composition of the present invention can be suitably used in machinery and equipment installed in high vacuum such as outer space. In addition, the bearings enclosed with the lubricant composition of the present invention can be suitably used in precision machinery, wind power generation equipment that is difficult to maintain, seismic isolation equipment, etc.

[0333] Furthermore, specific examples of bearings enclosed with the lubricant composition of the present invention include bearings used in automotive electrical components such as electric fan motors and wiper motors, rolling bearings used in drive systems for automotive engine auxiliaries such as water pumps and electromagnetic clutch devices, rolling bearings used in rotating devices such as small or large general-purpose motors for industrial machinery, high-speed and high-precision rotating bearings such as spindle bearings for machine tools, rolling bearings used in motors and rotating devices for household electrical products such as air-conditioning fan motors and washing machines, rolling bearings used in rotating parts of computer-related equipment such as HDD devices and DVD devices, rolling bearings used in rotating parts of office equipment such as copiers and automatic ticket gates, and axle bearings for trains and trucks.

[0334] The other components that may be included in the lubricant composition of the present invention within the range that does not impair the effects of the present invention are described in order. These are basically substances that are conventionally known as components contained in lubricants, and their content can be appropriately selected by those skilled in the art within the conventionally known range unless otherwise specified. In addition, any component may be used alone or in combination of two or more.

[0335] (Liquid Crystalline Compounds)

[0336] The compounds represented by formula (1) and (2) are liquid crystal compounds, and the lubricant composition of the present invention may contain other liquid crystal compounds.

[0337] Examples of such liquid crystal compounds include liquid crystal compounds that exhibit a smectic phase or a nematic phase, compounds having a structure of an alkylsulfonic acid or perfluorosulfonic acid film system, alkylcarboxylic acids, alkylsulfonic acids, etc. In addition, the lubricant composition of the present invention may contain liquid crystal compounds described in Japanese Patent No. 5916916 and Japanese Unexamined Patent Application No. 2017-105874.

[0338] (Base oil)

[0339] The lubricant composition of the present invention can be mixed with various conventionally known lubricant base oils for use.

[0340] Examples of the base oil include, but are not particularly limited to, mineral oil, highly purified mineral oil, synthetic hydrocarbon oil, paraffinic mineral oil, alkyl diphenyl ether oil, ester oil, silicone oil, naphthenic mineral oil, and fluorinated oil.

[0341] (Other additives)

[0342] In addition, examples of additives that can be added to the lubricant composition of the present invention include various additives used in lubricants such as bearing oils, gear oils and working oils, namely, extreme pressure agents, oriented adsorbents, antiwear agents, wear regulators, oiliness agents, antioxidants, viscosity index improvers, pour point depressants, detergents and dispersants, metal deactivators, corrosion inhibitors, rust inhibitors, defoaming agents, solid lubricants, etc.

[0343] Examples of the extreme pressure agent include chlorine compounds, sulfur compounds, phosphoric acid compounds, hydroxycarboxylic acid derivatives, and organic metal extreme pressure agents. The addition of the extreme pressure agent improves the wear resistance of the conductive lubricant of the present invention.

[0344] Examples of the above-mentioned alignment adsorbent include organic silane, organic titanium, organic aluminum, etc. represented by various coupling agents such as silane coupling agents, titanium coupling agents, and aluminum coupling agents. By adding the alignment adsorbent, the liquid crystal alignment of the liquid crystal compound contained in the lubricant composition of the present invention is enhanced, and the thickness and strength of the film formed by the lubricant composition of the present invention can be enhanced.

[0345] The lubricant composition of the present invention can be prepared by mixing the compounds represented by formula (1) and (2) and other components by a conventionally known method. An example of a method for preparing the lubricant composition of the present invention is as follows.

[0346] The components of the lubricant composition are mixed by a conventional method, and then subjected to a roll mill, degassing treatment, filter treatment, etc. as needed to obtain the lubricant composition of the present invention. Alternatively, the lubricant composition may be prepared by first mixing the oil component of the lubricant composition, then adding other components such as additives and mixing, and then subjecting the above-mentioned degassing treatment, etc. as needed.

[0347] [Example]

[0348] Hereinafter, more specific examples of the present invention will be described, but the present invention is not limited to these examples.

[0349] [Preparation of lubricant composition]

[0350] As a bicyclic liquid crystal compound, a mixture of compounds represented by the following formulae (6) to (8) was prepared.

[0351] The mixing ratio of the compounds represented by formulae (6) to (8) is approximately 1:2:1 (molar ratio).

[0352]

[0353] As a tricyclic liquid crystal compound, a mixture of compounds represented by the following formulae (3) to (5) was prepared.

[0354] The mixing ratio of the compounds represented by formulae (3) to (5) is approximately 1:2:1 (molar ratio).

[0355]

[0356] The two-ring liquid crystal compound and the three-ring liquid crystal compound prepared above were heated to 200° C. and mixed at various ratios to prepare lubricant compositions. The following tests were performed using the prepared lubricant compositions.

[0357] [Softness test at room temperature]

[0358] After the lubricant composition was cooled to room temperature (25° C.), it was stirred several times with a spatula and then sealed in a bearing. A ball spline bearing was used in the test.

[0359] Ball spline bearings such as Figure 4As shown, a small ball spline bearing 10 is provided with an outer cylinder 16 capable of linearly moving along an axis 14 by means of a plurality of rolling elements 12. A track groove 14a in which the plurality of rolling elements 12 rotate is formed on the outer peripheral surface of the axis 14 along the axial direction. The plurality of rolling elements 12 are held between the track groove 14a formed on the outer peripheral surface of the axis 14 and the inner surface of the outer cylinder 16. An end cap 18 for changing the direction of the plurality of rolling elements 12 is fixed to the end of the outer cylinder 16 by means of screw fixing or the like. The plurality of rolling elements 12 rotating along the track groove 14a change direction along the direction change path formed in the end cap 18, thereby forming an infinite loop.

[0360] When the lubricant composition is sealed in the bearing 10, the shaft 14 is pulled out from the outer cylinder 16, and then the lubricant composition is applied to the plurality of rolling elements 12 held inside the outer cylinder 16. After the lubricant composition is applied to the plurality of rolling elements 12, as shown in FIG. Figure 4 As shown, the outer cylinder 16 is assembled to the shaft 14 again.

[0361] Then, the lubricant composition is sealed in the bearing 10, and the softness of the lubricant composition at room temperature is determined by whether the rolling element can circulate. The determination criteria are as follows. It should be noted that a small ball spline bearing ("LSAG4" manufactured by Nippon Thompson Co., Ltd.) with a shaft diameter of 4 mm was used in the test.

[0362] A: The rolling body can circulate and the lubricant composition is very soft.

[0363] B: The rolling body can circulate and the lubricant composition has flexibility.

[0364] C: The rolling element cannot circulate, and the lubricant composition has no flexibility and is easily crushed.

[0365] Table 1 below shows the mixing ratio of the bicyclic liquid crystal compound and the tricyclic liquid crystal compound contained in the lubricant composition and the results of the softness test of the lubricant composition at room temperature.

[0366] [Table 1]

[0367] Softness test results at room temperature

[0368]

[0369] According to the results shown in Table 1, when more 3-ring liquid crystal compounds are included than 2-ring liquid crystal compounds, the softness of the lubricant composition tends to be improved. In particular, when the mixing ratio of the 2-ring liquid crystal compound is 70 or more (where the total of the 2-ring liquid crystal compound and the 3-ring liquid crystal compound is 100), the lubricant composition has sufficient softness and it is easy to seal the lubricant composition in the bearing. On the contrary, when the mixing ratio of the 2-ring liquid crystal compound is 10 or less, the lubricant composition becomes hard, so the rolling element cannot circulate in the bearing.

[0370] [Flowability test during heating]

[0371] A test was conducted to confirm the fluidity of the lubricant composition when it was heated. The apparatus used in the test is shown in FIG. Figure 5 .

[0372] In the test, first, the lubricant composition (about 5 mg) is attached to a glass slide. The inclination angle of the glass slide is set to 70°. The lubricant composition is attached to a position 20 mm from the upper end of the glass slide. After the lubricant composition is attached to the glass slide, the glass slide is heated in an oven until a specified temperature is reached. After the heated glass slide is placed for 10 minutes, the lubricant composition attached to the glass slide is visually observed to determine the fluidity of the lubricant composition. The judgment criteria are as follows.

[0373] ○: The lubricant composition did not flow onto the slide glass.

[0374] ×: The lubricant composition dripped on the slide glass.

[0375] The following Tables 2 and 3 show the mixing ratio (mass ratio) of the two-ring liquid crystal compound and the three-ring liquid crystal compound contained in the lubricant composition and the results of the fluidity test of the lubricant composition when heated. The sample numbers in Table 2 correspond to the sample numbers in Table 3.

[0376] [Table 2]

[0377]

[0378] [Table 3]

[0379]

[0380] The results shown in Tables 2 and 3 show that when the mixing ratio of the three-ring liquid crystal compound is 20 or more (wherein the total of the two-ring liquid crystal compound and the three-ring liquid crystal compound is 100), the lubricant composition does not sag even when the slide glass is heated to 110° C. Therefore, it was found that in order to obtain a lubricant composition that does not sag even at a high temperature (about 100° C.) during baking in a vacuum device, the mixing ratio of the three-ring liquid crystal compound is preferably 20 or more.

[0381] [Durability test at high temperature]

[0382] The lubricant composition is sealed into Figure 4 The bearing 10 shown was tested by continuously reciprocating the shaft 14 while the outer cylinder 16 was heated and fixed. The test was stopped when the vibration value of the bearing 10 during the test exceeded the set value or when the abnormal occurrence of wear powder was confirmed, and the travel distance at that time was measured. Other test conditions are as follows. In addition, as a comparative example, a commercially available cyclopentane vacuum lubricant and a fluorine vacuum lubricant were respectively sealed in the bearing, and the same test was performed. The results of these tests are shown in Table 4 below.

[0383] (Test conditions)

[0384] Heating temperature of outer cylinder: 80℃

[0385] Load: Medium preload

[0386] Stroke: 50mm

[0387] Maximum speed: 1m / s

[0388] Lubricant composition enclosed amount: 3 mg

[0389] [Table 4]

[0390]

[0391] The results shown in Table 4 show that when more 2-ring liquid crystal compounds are contained than 3-ring liquid crystal compounds, the durability of the lubricant composition at high temperatures is improved. In particular, it was found that when the mixing ratio of the 2-ring liquid crystal compound to the 3-ring liquid crystal compound is 80:20 to 60:40, the durability of the lubricant composition at high temperatures is significantly high. In addition, it was found that when the mixing ratio of the 2-ring liquid crystal compound is 40 or more (where the total of the 2-ring liquid crystal compound and the 3-ring liquid crystal compound is 100), a lubricant composition having a high-temperature durability equal to or higher than that of a commercially available vacuum lubricant can be obtained.

[0392] [Evaporation test at high temperature]

[0393] A lubricant composition having a mixing ratio (mass ratio) of 6:4 between the bicyclic liquid crystal compound and the tricyclic liquid crystal compound was prepared. The prepared lubricant composition was left at 100°C and atmospheric pressure for 770 hours, and the residual rate of the lubricant composition was measured according to the following formula.

[0394] Residual rate (%) = (residual amount of lubricant composition (g) / initial amount of lubricant composition (g)) × 100

[0395] In addition, as comparative examples, similar measurements were performed using commercially available cyclopentane vacuum lubricants and fluorine vacuum lubricants. The measurement results are shown in Table 5 below.

[0396] [Table 5]

[0397] Elapsed time (hours) 0 20 120 300 500 770 Lubricant composition (mixing ratio 6:4) 100% 100% 100% 100% 100% 100% Fluorine-based vacuum lubricant 100% 100% 100% 100% 100% 100% Cyclopentane vacuum lubricant 100% 98% 96% 94% 93% 92%

[0398] The results shown in Table 5 show that the lubricant composition of the present invention has a residual rate of 100% after 770 hours and hardly evaporates even at a high temperature of 100°C. On the other hand, the residual rate of the cyclopentane vacuum lubricant after 770 hours is 92%, and 8% of it is lost by evaporation. These results show that the lubricant composition of the present invention is very unlikely to evaporate, and therefore can be used continuously for a long time without replenishment, compared with general-purpose greases.

[0399] [Evaporation test in vacuum environment]

[0400] A lubricant composition having a mixing ratio of 6:4 (mass ratio) of a 2-ring liquid crystal compound to a 3-ring liquid crystal compound was prepared. The prepared lubricant composition was heated at 23°C and 4.0×10 -5 The lubricant composition was placed in a high vacuum atmosphere of 1000 Pa for 1092 hours, and the residual rate (%) of the lubricant composition was measured according to the above-mentioned formula. The measurement results are shown in Table 6 below.

[0401] [Table 6]

[0402]

[0403] The results shown in Table 6 show that the lubricant composition of the present invention has a residual rate of 100% after 1092 hours and hardly evaporates even in a high vacuum atmosphere. This result shows that the lubricant composition of the present invention is not easily evaporated in a high vacuum and can therefore stably exhibit its performance in a high vacuum environment such as space.

[0404] [Saturated vapor pressure measurement test]

[0405] A lubricant composition having a mixing ratio of 6:4 (mass ratio) of a 2-ring liquid crystal compound to a 3-ring liquid crystal compound was prepared. The saturated vapor pressure and mass changes of the prepared lubricant composition were measured using a saturated vapor pressure evaluation device (VPE-9000, manufactured by ULVAC, Inc.). The measurement conditions are as follows.

[0406] (Measurement conditions)

[0407] Collection amount: 20mg

[0408] Vacuum degree: 0.0012Pa

[0409] Heating rate: 2℃ / min

[0410] Evaporation start temperature: The temperature at which the mass decreases by 1%.

[0411] In addition, as a comparative example, the same measurement was performed using a commercially available cyclopentane vacuum lubricant. The measurement results are shown in Figure 6 .

[0412] like Figure 6 As shown in FIG. 1 , the evaporation start temperature of the lubricant composition of the present invention is 180° C., and the saturated vapor pressure (maximum vapor pressure) at 243° C. is 1.49×10 -1 Pa. In contrast, the evaporation start temperature of cyclopentane vacuum lubricant is 91°C, and the saturated vapor pressure (maximum vapor pressure) at 259°C is 2.26×10 -1 Pa. From these results, it was confirmed that the lubricant composition of the present invention is less likely to evaporate than commercially available vacuum lubricants.

[0413] [Pressure measurement test at elevated temperature]

[0414] A lubricant composition having a mixing ratio of 6:4 (mass ratio) of a 2-ring liquid crystal compound to a 3-ring liquid crystal compound was prepared. The pressure change (total pressure) when the prepared lubricant composition was heated was measured using a saturated vapor pressure evaluation device (VPE-9000, manufactured by ULVAC, Inc.). The measurement conditions were as follows.

[0415] (Measurement conditions)

[0416] Measurement temperature: room temperature ~ 200℃

[0417] Heating rate: 10℃ / min

[0418] Pressure at the start of measurement: about 1.0×10 -5 Pa

[0419] In addition, as a comparative example, the same measurement was performed using a commercially available cyclopentane vacuum lubricant and a fluorine vacuum lubricant. The measurement results are shown in Figure 7 .

[0420] like Figure 7 As shown in the figure, the total pressure of the lubricant composition of the present invention does not change substantially until about 200°C. In contrast, it can be confirmed that the total pressure of the cyclopentane vacuum lubricant rises sharply at about 90°C and evaporates easily. From these results, it can be confirmed that the lubricant composition of the present invention is much less likely to evaporate than commercially available cyclopentane vacuum lubricants, and the total pressure is stable at room temperature to 200°C.

[0421] [Dust generation test]

[0422] A test was conducted to evaluate the dust generation of the lubricant composition by continuously operating a linear motion guide unit enclosed with the lubricant composition. The linear motion guide unit used in the test is shown in FIG. Figure 8 .

[0423] like Figure 8 As shown, the linear motion guide unit 20 is a small linear motion guide unit ("LWL9" manufactured by Nippon Thompson Co., Ltd.) having a slide 26 that can move linearly along a slide rail 24 with the help of a plurality of rolling elements 22. Track grooves 24a on which the plurality of rolling elements 22 rotate are formed on both sides of the slide rail 24 along the length direction. The plurality of rolling elements 22 are retained between the track grooves 24a formed on both sides of the slide rail 24 and the inner surface of the slide 26. An end cap 28 for converting the directions of the plurality of rolling elements 22 is fixed to the end of the slide 26 by means of screw fixing or the like. The plurality of rolling elements 22 that rotate along the track grooves 24a convert their directions along the direction conversion path formed in the end cap 28, thereby forming an infinite loop.

[0424] In the experiment, first, a lubricant composition having a mixing ratio of 6:4 (mass ratio) of a 2-ring liquid crystal compound to a 3-ring liquid crystal compound and a lubricant composition having a mixing ratio of 8:2 (mass ratio) of a 2-ring liquid crystal compound to a 3-ring liquid crystal compound were prepared. The prepared lubricant compositions were respectively sealed in the linear motion guide unit 20. When the lubricant composition was sealed in the linear motion guide unit 20, after the slide rail 24 was pulled out from the slide 26, the lubricant composition was applied to the plurality of rolling elements 22 held on the inner side of the slide 26. After the lubricant composition was applied to the plurality of rolling elements 22, as Figure 8 As shown, the slide member 26 is assembled to the slide rail 24 again.

[0425] Then, the linear motion guide unit 20 enclosed with the lubricant composition is continuously reciprocated in the chamber. During the operation of the linear motion guide unit 20, clean air passing through the HEPA filter is fed into the chamber in a downward manner, and the number of particles in the exhaust gas discharged from the chamber is measured in each particle size range shown in Table 7 below. The number of particles is measured using a particle counter (Rion Co., Ltd., KC-22A). Other measurement conditions are as follows.

[0426] (Measurement conditions)

[0427] Moving distance of linear motion guide unit: 500mm

[0428] Maximum speed: 1m / s

[0429] Load: 80N

[0430] Air volume (sampling air volume): 0.38m 3 / minute

[0431] Measurement time: 24 hours

[0432] In addition, as a comparative example, a commercially available cyclopentane vacuum lubricant and a hydrocarbon low dust generation lubricant were respectively sealed in the linear motion guide unit 20, and the same test was performed. The results of these tests are shown in the following Tables 7 and 8. Fig. 9 .

[0433] [Table 7]

[0434]

[0435] According to Table 7 and Fig. 9 The results shown confirm that the dust generation of the lubricant composition of the present invention is extremely small and that the dust generation is sufficiently low compared to commercially available cyclopentane vacuum lubricants or hydrocarbon low dust generation lubricants. It is also confirmed that the dust generation of the lubricant composition (6:4) with less bicyclic liquid crystal compounds is even lower.

[0436] The mixing ratio of the 2-ring liquid crystal compound to the 3-ring liquid crystal compound in the lubricating composition of the present invention is 95:5 to 15:85 by mass ratio. The lubricating composition of the present invention preferably contains more 2-ring liquid crystal compounds than 3-ring liquid crystal compounds. The mixing ratio of the 2-ring liquid crystal compound to the 3-ring liquid crystal compound can more preferably be 80:20 to 60:40.

[0437] [Explanation of Reference Numerals]

[0438] 10 Bearings

[0439] 12 Rolling elements

[0440] 14 Axis

[0441] 16 outer cylinder

[0442] 18 End cap

[0443] 20 Linear motion guide unit

[0444] 22 Rolling elements

[0445] 24 Slide rails

[0446] 26 Slide

[0447] 28 End cap

[0448] The present inventors have found that a liquid crystal mixture having excellent performance as a lubricant can be obtained by mixing a two-ring liquid crystal compound and a three-ring liquid crystal compound having a certain specific structure, and have completed the present invention. That is, the present invention includes the following. [1]

[0450] A lubricant composition comprising: at least one of the two-ring liquid crystal compounds represented by the following formula (1), at least one of the three-ring liquid crystal compounds represented by the following formula (2), and at least one of the three-ring liquid crystal compounds represented by the following formula (3).

[0451] Formula (1):

[0452]

[0453] [Wherein,

[0454] R 1 and R 2 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)]

[0455] Formula (2):

[0456]

[0457] [Wherein,

[0458] R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20),

[0459] R 12, R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20)]

[0460] Formula (3):

[0461]

[0462] [Wherein,

[0463] R 31 and R 41 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0464] R 32 , R 33 , R 42 and R 43 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)] [2]

[0466] The lubricant composition according to [1], wherein in the formula (1), 1≤n≤15, and R' is a methyl group. [3]

[0468] The lubricant composition according to [1] or [2], wherein in the formula (3), R 32 or R 33 , and R 42 or R 43 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight chain C n H 2n+1 , 1≤n≤15, R' is methyl). [4]

[0470] The lubricant composition according to any one of [1] to [3], wherein the tricyclic liquid crystal compound represented by the formula (2) is at least one of the compounds represented by the following formulas (4) to (6).

[0471] [5]

[0473] The lubricant composition according to any one of [1] to [4], wherein the tricyclic liquid crystal compound represented by the formula (3) is at least one of the compounds represented by the following formulas (7) and (8).

[0474] [6]

[0476] The lubricant composition according to any one of [1] to [5], wherein the mixing ratio of the two-ring liquid crystal compound represented by the formula (1), the three-ring liquid crystal compound represented by the formula (2), and the three-ring liquid crystal compound represented by the formula (3) is 60:40 to 4:96 in terms of mass ratio. [7]

[0478] The lubricant composition according to any one of [1] to [6], wherein the content of the bicyclic liquid crystal compound is 4 to 40 wt %, and the content of the tricyclic liquid crystal compound represented by formula (3) is 20 to 64 wt %. [8]

[0480] A bearing enclosed with the lubricant composition described in any one of [1] to [7].

[0481] [Effects of the Invention]

[0482] According to the present invention, there can be provided a lubricant composition suitable for use in a clean environment, under a high vacuum, or at a high temperature, and a bearing enclosing the lubricant composition.

[0483] According to the present invention, there is provided a lubricant composition comprising: at least one of the two-ring liquid crystal compounds represented by the following formula (1), at least one of the three-ring liquid crystal compounds represented by the following formula (2), and at least one of the three-ring liquid crystal compounds represented by the following formula (3).

[0484] Formula (1):

[0485]

[0486] [Wherein,

[0487] R 1 and R 2 The same or different, is a group -OCH 2CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)]

[0488] Formula (2):

[0489]

[0490] [Wherein,

[0491] R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20),

[0492] R 12 , R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20)]

[0493] Formula (3):

[0494]

[0495] [Wherein,

[0496] R 31 and R 41 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0497] R 32 , R 33 , R 42 and R 43 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)]

[0498] In formulas (1) to (3), R 1 , R 2 , R 11 , R 12 , R 13 , R 21 , R 22 , R 23 , R 31 , R 32 , R 33 , R 41 , R 42 and R 43 Connected to the core structure, it is a chain group that takes on the lubricity of the molecule. 1 , R 2 , R 11 , R 12 , R 13 , R 21 , R 22 , R 23 , R 31 , R 32 , R 33 , R 41 , R 42 and R 43 , thereby adjusting the overall size (long diameter) and polarity of the molecule.

[0499] Examples of R in formulas (1) to (3) include n-butyl, isobutyl, sec-butyl, tert-butyl, n-pentyl, 1-methyl-n-butyl, 2-methyl-n-butyl, 3-methyl-n-butyl, 1,1-dimethyl-n-propyl, 1,2-dimethyl-n-propyl, 2,2-dimethyl-n-propyl, 1-ethyl-n-propyl, n-hexyl, 1-methyl-n-pentyl, 2-methyl-n-pentyl, 3-methyl-n-pentyl, 4-methyl-n-pentyl, 1,1-dimethyl-n-butyl, 1,2-dimethyl-n-butyl, 1,3-dimethyl 1-ethyl-n-butyl, 2,2-dimethyl-n-butyl, 2,3-dimethyl-n-butyl, 3,3-dimethyl-n-butyl, 1-ethyl-n-butyl, 2-ethyl-n-butyl, 1,1,2-trimethyl-n-propyl, 1,2,2-trimethyl-n-propyl, 1-ethyl-1-methyl-n-propyl, 1-ethyl-2-methyl-n-propyl, n-heptyl, 1-methyl-n-hexyl, 2-methyl-n-hexyl, 3-methyl-n-hexyl, 1,1-dimethyl-n-pentyl, 1,2-dimethyl-n-pentyl, 1,3-dimethyl-n-pentyl, 2 ,2-dimethyl-n-pentyl, 2,3-dimethyl-n-pentyl, 3,3-dimethyl-n-pentyl, 1-ethyl-n-pentyl, 2-ethyl-n-pentyl, 3-ethyl-n-pentyl, 1-methyl-1-ethyl-n-butyl, 1-methyl-2-ethyl-n-butyl, 1-ethyl-2-methyl-n-butyl, 2-methyl-2-ethyl-n-butyl, 2-ethyl-3-methyl-n-butyl, n-octyl, 1-methyl-n-heptyl, 2-methyl-n-heptyl, 3-methyl-n-heptyl, 1,1-dimethyl-n-hexyl, 1,2-dimethyl- n-Hexyl, 1,3-dimethyl-n-hexyl, 2,2-dimethyl-n-hexyl, 2,3-dimethyl-n-hexyl, 3,3-dimethyl-n-hexyl, 1-ethyl-n-hexyl, 2-ethyl-n-hexyl, 3-ethyl-n-hexyl, 1-methyl-1-ethyl-n-pentyl, 1-methyl-2-ethyl-n-pentyl, 1-methyl-3-ethyl-n-pentyl, 2-methyl-2-ethyl-n-pentyl, 2-methyl-3-ethyl-n-pentyl, 3-methyl-3-ethyl-n-pentyl, n-nonyl, n-decyl, n-undecyl, n-dodecyl, etc.

[0500] In formula (1), R 1 and R 2 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, preferably 1≤n≤15, more preferably 4≤n≤12, particularly preferably 8≤n≤10, R' is methyl or ethyl).

[0501] In formula (1), preferably, 1≤n≤15, and R' is a methyl group.

[0502] In formula (2), R 11 and R 21 The same or different, is a group -OR (R is a straight chain or branched chain C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 8≤n≤12).

[0503] In formula (2), R 12 , R 13 , R 22 and R 23 are the same or different, are hydrogen, or a group -OR (R is a linear or branched C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 8≤n≤12).

[0504] In formula (3), R 31 and R 41 The same or different, is a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 4≤n≤12, particularly preferably 6≤n≤8, R' is methyl or ethyl).

[0505] In formula (3), R 32 , R 33 , R 42 and R 43 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, preferably 4≤n≤16, more preferably 4≤n≤12, particularly preferably 6≤n≤8, R' is methyl or ethyl).

[0506] In formula (3), preferably R 32 or R 33 , and R 42 or R 43 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight chain C nH 2n+1 , 1≤n≤15, R' is methyl).

[0507] The three-ring liquid crystal compound represented by formula (2) is preferably at least one of the compounds represented by the following formulae (4) to (6).

[0508]

[0509] The three-ring liquid crystal compound represented by formula (3) is preferably at least one of the compounds represented by the following formulas (7) and (8).

[0510]

[0511] The bicyclic liquid crystal compound represented by formula (1) is preferably at least one of the compounds represented by the following formulae (9) to (11).

[0512]

[0513] In the present invention, the three-ring liquid crystal compound represented by formula (2) can be used alone or in combination of two or more thereof. For example, any of the compounds represented by formulas (4) to (6) can be used alone or in combination of two or more thereof. In addition, all of the compounds represented by formulas (4) to (6) can be used in combination.

[0514] In the present invention, the three-ring liquid crystal compound represented by formula (3) may be used alone or in combination of two or more. For example, any of the compounds represented by formula (7) and (8) may be used alone or in combination.

[0515] In the present invention, the two-ring liquid crystal compound represented by formula (1) can be used alone or as a mixture of two or more thereof. For example, any of the compounds represented by formulas (9) to (11) can be used alone or as a mixture of two or more thereof. In addition, all of the compounds represented by formulas (9) to (11) can be mixed and used.

[0516] The method for producing the 2-ring liquid crystal compound represented by formula (1) and the 3-ring liquid crystal compound represented by formula (2) is not particularly limited, and they can also be produced by combining known reactions. For example, they can be produced according to the method described in Japanese Patent Application Publication No. 2017-105874.

[0517] The method for producing the three-ring liquid crystal compound represented by formula (3) is not particularly limited, and the compound can be produced by combining known reactions. An example of the method for producing the three-ring liquid crystal compound represented by formula (3) is as follows.

[0518] The following method can be used: using an alcohol compound (such as R 31 -OH), phenolic compounds (e.g. HO-[3-ring skeleton structure]-OH) and alkali metals, alkali metal alkoxides, and halogen compounds (e.g. R 31 -X, X-[3-ring skeleton structure]-X (X is a halogen atom such as a chlorine atom, a bromine atom or an iodine atom)). For example, it can be prepared according to the method described in Japanese Patent No. 5916916.

[0519] In particular, the three-ring liquid crystal compound represented by formula (3) can be prepared as follows.

[0520] At least one compound represented by the following formula

[0521]

[0522] [Wherein,

[0523] R 31 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0524] R 32 and R 33 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)],

[0525] At least one compound represented by the following formula

[0526]

[0527] [Wherein,

[0528] R 41 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0529] R 42and R 43 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)],

[0530] And the compound represented by the following formula

[0531]

[0532] The reaction is carried out under appropriate reaction conditions to obtain a mixture of the following compounds in a molar ratio of 1:2:1.

[0533]

[0534] [Where R 31 , R 32 , R 33 , R 41 , R 42 and R 43 As defined above]

[0535] Examples of the alkali metal include potassium carbonate, potassium hydroxide, sodium hydroxide, and the like. Examples of the alkali metal alkoxide include sodium ethoxide, sodium methoxide, sodium tert-butoxide, potassium tert-butoxide, and the like.

[0536] In addition, various conventionally known organic solvents can be used in the above reaction, for example, diethyl ether, tetrahydrofuran (THF), acetone, and toluene can be used.

[0537] As another method, it can also be prepared as follows.

[0538] At least one compound represented by the following formula

[0539]

[0540] [Wherein,

[0541] R 31 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0542] R 32 and R 33The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)],

[0543] At least one compound represented by the following formula

[0544]

[0545] [Wherein,

[0546] R 41 For the group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl),

[0547] R 42 and R 43 The same or different, is hydrogen, or a group -OCH 2 CH 2 CH(R')CH 2 CH 2 OR (R is a straight or branched chain C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl)],

[0548] And terephthalaldehyde shown in the following formula

[0549]

[0550] The reaction is carried out under appropriate reaction conditions to obtain a mixture of the following compounds in a molar ratio of 1:2:1.

[0551]

[0552] [Where R 31 , R 32 , R 33 , R 41 , R 42 and R 43 As defined above]

[0553] The lubricant composition of the present invention is very unlikely to evaporate (for example, the residual rate after 600 hours in an atmosphere at a temperature of 100° C. is 95% or more), and therefore has the advantage of being able to be used continuously for a long time without replenishment, compared to general-purpose greases.

[0554] The lubricant composition of the present invention is not easily evaporated under high vacuum (for example, at a temperature of 25°C and a pressure of 10 -5 Pa atmosphere after 1000 hours, the residual rate is 95% or more), so it can be suitably used in high vacuum conditions such as outer space.

[0555] The lubricant composition of the present invention has extremely low dust generation and is therefore suitable for use in, for example, a semiconductor manufacturing apparatus installed in a clean room requiring a high degree of cleanliness.

[0556] The lubricant composition of the present invention is not easy to evaporate and has low dust generation. In addition, the lubricant composition of the present invention can stably exert its performance under high vacuum and high temperature. Therefore, the lubricant composition of the present invention can exert excellent performance as a lubricant for bearings.

[0557] The bearing encapsulated with the lubricant composition of the present invention can be suitably used in, for example, a semiconductor manufacturing device installed in a clean room. In addition, the bearing encapsulated with the lubricant composition of the present invention can be suitably used in machinery and equipment installed in a high vacuum such as outer space. In addition, the bearing encapsulated with the lubricant composition of the present invention can be suitably used in precision machinery, wind power generation equipment that is difficult to maintain, seismic isolation equipment, etc.

[0558] Furthermore, specific examples of bearings enclosed with the lubricant composition of the present invention include bearings used in automotive electrical components such as electric fan motors and wiper motors, rolling bearings used in drive systems for automotive engine auxiliaries such as water pumps and electromagnetic clutch devices, rolling bearings used in rotating devices such as small or large general-purpose motors for industrial machinery, high-speed and high-precision rotating bearings such as spindle bearings for machine tools, rolling bearings used in motors and rotating devices for household electrical products such as air-conditioning fan motors and washing machines, rolling bearings used in rotating parts of computer-related equipment such as HDD devices and DVD devices, rolling bearings used in rotating parts of office equipment such as copiers and automatic ticket gates, and axle bearings for trains and trucks.

[0559] The other components that may be included in the lubricant composition of the present invention within the range that does not impair the effects of the present invention are described in order. These are basically substances that are conventionally known as components contained in lubricants, and their contents can be appropriately selected by those skilled in the art within the conventionally known range unless otherwise specified. In addition, any component may be used alone or in combination of two or more.

[0560] (Liquid Crystalline Compounds)

[0561] The compounds represented by formulae (1) to (3) are liquid crystal compounds, and the lubricant composition of the present invention may contain other liquid crystal compounds.

[0562] Examples of such liquid crystal compounds include liquid crystal compounds that exhibit a smectic phase or a nematic phase, compounds having a structure of an alkylsulfonic acid or perfluorosulfonic acid film system, alkylcarboxylic acids, alkylsulfonic acids, etc. In addition, the lubricant composition of the present invention may contain liquid crystal compounds described in Japanese Patent No. 5916916 and Japanese Unexamined Patent Application No. 2017-105874.

[0563] (Base oil)

[0564] The lubricant composition of the present invention can be mixed with various conventionally known lubricant base oils for use.

[0565] Examples of the base oil include, but are not particularly limited to, mineral oil, highly purified mineral oil, synthetic hydrocarbon oil, paraffinic mineral oil, alkyl diphenyl ether oil, ester oil, silicone oil, naphthenic mineral oil, and fluorinated oil.

[0566] (Other additives)

[0567] In addition, examples of additives that can be added to the lubricant composition of the present invention include various additives used in lubricants such as bearing oils, gear oils and working oils, namely, extreme pressure agents, oriented adsorbents, antiwear agents, wear regulators, oiliness agents, antioxidants, viscosity index improvers, pour point depressants, detergent dispersants, metal deactivators, corrosion inhibitors, rust inhibitors, defoaming agents, solid lubricants, etc.

[0568] Examples of the extreme pressure agent include chlorine compounds, sulfur compounds, phosphoric acid compounds, hydroxycarboxylic acid derivatives, and organic metal extreme pressure agents. The addition of the extreme pressure agent improves the wear resistance of the conductive lubricant of the present invention.

[0569] Examples of the above-mentioned alignment adsorbent include organic silane, organic titanium, organic aluminum, etc. represented by various coupling agents such as silane coupling agents, titanium coupling agents, and aluminum coupling agents. By adding the alignment adsorbent, the liquid crystal alignment of the liquid crystal compound contained in the lubricant composition of the present invention is enhanced, and the thickness and strength of the film formed by the lubricant composition of the present invention can be enhanced.

[0570] The lubricant composition of the present invention can be prepared by mixing the compounds represented by formulae (1) to (3) and other components by a conventionally known method. An example of a method for preparing the lubricant composition of the present invention is as follows.

[0571] The lubricant composition of the present invention is obtained by mixing the components of the lubricant composition in a conventional manner, and then, if necessary, performing a roll mill, a degassing treatment, a filter treatment, etc. Alternatively, the lubricant composition may be prepared by first mixing the oil component of the lubricant composition, then adding and mixing other components such as additives, and performing the above-mentioned degassing treatment, etc., if necessary.

[0572] [Example]

[0573] Hereinafter, more specific examples of the present invention will be described, but the present invention is not limited to these examples.

[0574] [Preparation of lubricant composition]

[0575] As the bicyclic liquid crystal compound represented by formula (1), a mixture of compounds represented by the following formulae (9) to (11) was prepared. The mixing ratio of the compounds represented by formulae (9) to (11) was approximately 1:2:1 (molar ratio).

[0576]

[0577] As the tricyclic liquid crystal compound represented by formula (2), a mixture of compounds represented by the following formulae (4) to (6) was prepared. The mixing ratio of the compounds represented by formulae (4) to (6) was approximately 1:2:1 (molar ratio).

[0578]

[0579] As the three-ring liquid crystal compound represented by the formula (3), the compounds represented by the following formulae (7) and (8) were prepared.

[0580]

[0581] That is, a two-ring liquid crystal compound (a mixture of compounds represented by formulae (9) to (11)) and three types of three-ring liquid crystal compounds are prepared. The three types of three-ring liquid crystal compounds are hereinafter referred to as follows.

[0582] Tricyclic liquid crystal compound LC1: a mixture of compounds represented by formula (4) to (6)

[0583] Tricyclic liquid crystal compound LC2: a compound represented by formula (7)

[0584] Tricyclic liquid crystal compound LC3: a compound represented by formula (8)

[0585] The two-ring liquid crystal compound and the three-ring liquid crystal compounds LC1 to LC3 prepared above were heated to 200° C. and mixed at various ratios to prepare lubricant compositions (sample numbers 1 to 23) shown in the following Table 1. The numbers in the table represent mass %.

[0586] [Table 1]

[0587]

[0588] Using the prepared lubricant composition, the following various tests were carried out.

[0589] [Softness test at room temperature]

[0590] After cooling the lubricant composition to room temperature (25° C.), the composition was stirred several times with a spatula and then sealed in a bearing. A ball spline bearing was used in the test.

[0591] Ball spline bearings such as Fig.10 As shown, a small ball spline bearing 10 is provided with an outer cylinder 16 capable of linearly moving along an axis 14 by means of a plurality of rolling elements 12. A track groove 14a in which the plurality of rolling elements 12 rotate is formed on the outer peripheral surface of the axis 14 along the axial direction. The plurality of rolling elements 12 are held between the track groove 14a formed on the outer peripheral surface of the axis 14 and the inner surface of the outer cylinder 16. An end cap 18 for changing the direction of the plurality of rolling elements 12 is fixed to the end of the outer cylinder 16 by means of screw fixing or the like. The plurality of rolling elements 12 rotating along the track groove 14a change their direction along the direction change path formed in the end cap 18, thereby forming an infinite loop.

[0592] When the lubricant composition is sealed in the bearing 10, the shaft 14 is pulled out from the outer cylinder 16, and then the lubricant composition is applied to the plurality of rolling elements 12 held inside the outer cylinder 16. After the lubricant composition is applied to the plurality of rolling elements 12, as shown in FIG. Fig.10 As shown, the outer cylinder 16 is assembled to the shaft 14 again.

[0593] Then, the lubricant composition is sealed in the bearing 10, and the softness of the lubricant composition at room temperature is determined by whether the rolling element can circulate. The determination criteria are as follows. It should be noted that a small ball spline bearing ("LSAG4" manufactured by Nippon Thompson Co., Ltd.) with a shaft diameter of 4 mm was used in the test.

[0594] A: The rolling body can circulate and the lubricant composition is very soft.

[0595] B: The rolling body can circulate and the lubricant composition has flexibility.

[0596] C: The rolling element cannot circulate, and the lubricant composition has no flexibility and is easily crushed.

[0597] Table 1 above shows the results of the softness test of the lubricant composition at room temperature.

[0598] According to the results shown in Table 1, the lubricant composition of the present invention (sample numbers 2, 3, 4, 6, 7, 8, 10, 11, 12, 14, 15, 16, 18, 19, 20, and 21) containing a 2-ring liquid crystal compound, a 3-ring liquid crystal compound LC1, and at least one of the 3-ring liquid crystal compounds LC2 and LC3 has moderate flexibility, and even if sealed in a bearing, the rolling body can circulate.

[0599] In particular, when the total mixing ratio of the 2-ring liquid crystal compound and the 3-ring liquid crystal compounds LC1 to LC3 is 60:40 to 4:96 by mass ratio (sample numbers 2, 3, 4, 6, 7, 8, 10, 11, 12, 14, 15, 16, 18, 19, 20, and 21), the lubricant composition has sufficient softness and is easy to seal in the bearing.

[0600] [Flowability test during heating]

[0601] A test was conducted to confirm the fluidity of the lubricant composition when it was heated. The apparatus used in the test is shown in FIG. Fig.11 .

[0602] In the test, first, the lubricant composition (about 5 mg) is attached to a glass slide. The inclination angle of the glass slide is set to 70°. The lubricant composition is attached to a position 20 mm from the upper end of the glass slide. After the lubricant composition is attached to the glass slide, the glass slide is heated in an oven until a specified temperature is reached. After the heated glass slide is placed for 10 minutes, the lubricant composition attached to the glass slide is visually observed to determine the fluidity of the lubricant composition. The judgment criteria are as follows.

[0603] ○: The lubricant composition did not sag on the slide glass.

[0604] ×: The lubricant composition sagged on the slide glass.

[0605] The results of the fluidity test of the lubricant composition during heating are shown in the following Table 2. The sample numbers in Table 2 correspond to the sample numbers in Table 1.

[0606] [Table 2]

[0607]

[0608] The results shown in Table 2 show that when the content of the dicyclic liquid crystal compound in the lubricant composition of the present invention exceeds 45 wt % (sample numbers 2, 3, and 4), it melts (liquefies) and sags when heated to 115° C. Therefore, it was found that in order to obtain a lubricant composition that does not sag even at a high temperature (about 100° C.) during baking in a vacuum device, the content of the dicyclic liquid crystal compound contained in the lubricant composition is preferably 4 to 40 wt %.

[0609] The above test results indicate that in order to obtain a lubricant composition that is easily sealed into a bearing at room temperature and does not drip from the bearing even at a high temperature of 100°C, for example, the content of the 2-ring liquid crystal compound is preferably 4 to 40 wt%, and the content of the 3-ring liquid crystal compounds LC2 and LC3 is preferably 20 to 64 wt%.

[0610] [Durability test at high temperature]

[0611] The two-ring liquid crystal compound prepared above and the three-ring liquid crystal compounds LC1 to LC3 were mixed in the mass ratio shown in Table 3 below to prepare a lubricant composition. The prepared lubricant composition was sealed in Fig.10 The bearing 10 shown was tested by continuously reciprocating the shaft 14 while the outer cylinder 16 was heated and fixed. When the vibration value of the bearing 10 during the test exceeded the set value or when the abnormal occurrence of wear powder was confirmed, the test was stopped and the travel distance at that time was measured. Other test conditions are as follows. In addition, as a comparative example. A commercially available cyclopentane vacuum lubricant and a fluorine vacuum lubricant were respectively sealed in the bearing, and the same test was carried out. The results of these tests are shown in Table 3 below.

[0612] (Test conditions)

[0613] Heating temperature of outer cylinder: 80℃

[0614] Load: Medium preload

[0615] Stroke: 50mm

[0616] Maximum speed: 1m / s

[0617] Lubricant composition enclosed amount: 3 mg

[0618] [Table 3]

[0619]

[0620] From the results shown in Table 3, it was confirmed that the lubricant composition of the present invention containing the bicyclic liquid crystal compound and the tricyclic liquid crystal compounds LC1 to LC3 has sufficient durability at high temperatures as a lubricant for bearings.

[0621] [Pressure measurement test at elevated temperature]

[0622] A lubricant composition (1) was prepared in which the mixing ratio of the 2-ring liquid crystal compound and the 3-ring liquid crystal compound LC1 was 60:40 by mass ratio. In addition, a lubricant composition (2) was prepared in which the mixing ratio of the 2-ring liquid crystal compound, the 3-ring liquid crystal compound LC1, the 3-ring liquid crystal compound LC2, and the 3-ring liquid crystal compound LC3 was 1:1:1:1 by mass ratio. The pressure change (total pressure) when the prepared lubricant composition was heated was measured using a saturated vapor pressure evaluation device (VPE-9000, manufactured by ULVAC, Inc.). The measurement conditions are as follows.

[0623] (Measurement conditions)

[0624] Measurement temperature: room temperature ~ 200℃

[0625] Heating rate: 10℃ / min

[0626] Pressure at the start of measurement: about 1.0×10 -5 Pa

[0627] In addition, as a comparative example, the same measurement was performed using a commercially available cyclopentane vacuum lubricant and a fluorine vacuum lubricant. The measurement results are shown in Fig.12 .

[0628] like Fig.12 As shown in the figure, the total pressure of the lubricant composition (2) of the present invention does not change substantially until about 200°C. In contrast, it can be confirmed that the total pressure of the cyclopentane vacuum lubricant rises sharply at about 90°C and evaporates easily. From these results, it can be confirmed that the lubricant composition of the present invention is less likely to evaporate than commercially available cyclopentane vacuum lubricants, and the total pressure is stable at room temperature to 200°C.

[0629] [Dust generation test]

[0630] A test was conducted to evaluate the dust generation of the lubricant composition by continuously operating a linear motion guide unit enclosed with the lubricant composition. The linear motion guide unit used in the test is shown in FIG. Fig.13 .

[0631] like Fig.13As shown, the linear motion guide unit 20 is a small linear motion guide unit ("LWL9" manufactured by Nippon Thompson Co., Ltd.) having a slide 26 that can move linearly along a slide rail 24 with the help of a plurality of rolling elements 22. Track grooves 24a on which the plurality of rolling elements 22 rotate are formed on both sides of the slide rail 24 along the length direction. The plurality of rolling elements 22 are retained between the track grooves 24a formed on both sides of the slide rail 24 and the inner surface of the slide 26. An end cap 28 for changing the direction of the plurality of rolling elements 22 is fixed to the end of the slide 26 by means of threaded fixing or the like. The plurality of rolling elements 22 rotating along the track grooves 24a change direction along the direction change path formed in the end cap 28, thereby forming an infinite loop.

[0632] In the test, first, the following three types of lubricant compositions were prepared.

[0633] Lubricant composition (1): A lubricant composition in which the mixing ratio of the two-ring liquid crystal compound and the three-ring liquid crystal compound LC1 is 60:40 by mass ratio

[0634] Lubricant composition (2): a lubricant composition having a mixing ratio of 1:1:1:1 of a 2-ring liquid crystal compound, a 3-ring liquid crystal compound LC1, a 3-ring liquid crystal compound LC2, and a 3-ring liquid crystal compound LC3 by mass ratio

[0635] Lubricant composition (3): A lubricant composition in which the mixing ratio of the two-ring liquid crystal compound and the three-ring liquid crystal compound LC1 is 80:20 by mass ratio

[0636] The prepared lubricant composition is sealed in each linear motion guide unit 20. When the lubricant composition is sealed in the linear motion guide unit 20, after the slide rail 24 is pulled out from the slider 26, the lubricant composition is applied to the plurality of rolling elements 22 held inside the slider 26. After the lubricant composition is applied to the plurality of rolling elements 22, as shown in FIG. Fig.13 As shown, the slide member 26 is assembled to the slide rail 24 again.

[0637] Then, the linear motion guide unit 20 enclosed with the lubricant composition is continuously reciprocated in the chamber. During the operation of the linear motion guide unit 20, clean air passing through the HEPA filter is fed into the chamber in a downward manner, and the number of particles in the exhaust gas discharged from the chamber is measured in each particle size range shown in Table 4 below. The number of particles is measured using a particle counter (Rion Co., Ltd., KC-22A). Other measurement conditions are as follows.

[0638] (Measurement conditions)

[0639] Moving distance of linear motion guide unit: 500mm

[0640] Maximum speed: 1m / s

[0641] Load: 80N

[0642] Air volume (sampling air volume): 0.38m 3 / minute

[0643] Measurement time: 24 hours

[0644] As a comparative example, a commercially available cyclopentane vacuum lubricant and a hydrocarbon low dust generating lubricant were respectively sealed in the linear motion guide unit 20, and the same test was performed. The results of these tests are shown in the following Tables 4 and Fig.14 .

[0645] [Table 4]

[0646]

[0647] According to Table 4 and Fig.14 The results shown confirm that the lubricant composition (2) of the present invention generates much less dust than the other lubricant compositions (1) and (3), and has excellent performance as a lubricant for bearings used in a clean environment, for example.

[0648] Furthermore, it was confirmed that the lubricant composition (2) of the present invention has sufficiently low dust generation properties compared to commercially available cyclopentane-based vacuum lubricants or hydrocarbon-based low-dust-generating lubricants.

[0649] Description of Reference Numerals

[0650] 10 Bearings

[0651] 12 rolling elements

[0652] 14 axis

[0653] 16 outer cylinder

[0654] 18 End cap

[0655] 20 Linear motion guide unit

[0656] 22 rolling element

[0657] 24 slide rails

[0658] 26 Slides

[0659] 28 End cap

Claims

1. A lubricant composition comprising a 2-ring liquid crystal compound and a 3-ring liquid crystal compound, wherein the 2-ring liquid crystal compound contains only at least one of the 2-ring liquid crystal compounds represented by the following formula (1), and the 3-ring liquid crystal compound contains only at least one of the 3-ring liquid crystal compounds represented by the following formula (2), wherein the mixing ratio of the 2-ring liquid crystal compound to the 3-ring liquid crystal compound is 95:5 to 15:85 in terms of mass ratio, Formula (1): In formula (1), R 1 and R 2 The same or different groups are -OCH2CH2CH(R')CH2CH2OR, wherein R is a linear or branched C n H 2n+1 , 1≤n≤20, R' is methyl or ethyl, Formula (2): In formula (2), R 11 and R 21 The same or different groups are -OR, wherein R is a linear or branched C n H 2n+1 , 1≤n≤20, R 12 , R 13 , R 22 and R 23 are the same or different and are hydrogen or a group -OR, wherein R is a linear or branched C n H 2n+1 , 1≤n≤20.

2. The lubricant composition according to claim 1, wherein In the above formula (1), 1≤n≤15, and R' is a methyl group.

3. The lubricant composition according to claim 1 or 2, wherein The tricyclic liquid crystal compound is at least one of the compounds represented by the following formulae (3) to (5), 4 . The lubricant composition according to claim 1 , comprising more of the 2-ring liquid crystal compound than the 3-ring liquid crystal compound. 5 . The lubricant composition according to claim 1 , wherein the lubricant composition has a residual rate of 95% or more after 600 hours in an atmosphere at a temperature of 100° C.

6. The lubricant composition according to claim 1 or 2, which is -5 The remaining rate after 1000 hours in the Pa atmosphere was 95% or more. 7 . A bearing enclosed with the lubricant composition according to claim 1 .

Citation Information

Patent Citations

  • Conductive lubricant

    CN114854472A

  • Mud injector

    JP1984016916A

  • Lubricant composition

    JP1994128582A

  • Grease composition and rolling device obtained using the same

    JP2004359848A

  • Semisolid lubricant composition

    JP2005139398A